Hydride of block copolymer, resin composition, gel composition, cable filler, cable, cosmetic, lubricating oil, grease, and method for producing hydride of block copolymer

By using hydrides of block copolymers of specific structures in hydrogenated styrene-based elastomers, the problems of insufficient flexibility and rubber elasticity at low temperatures are solved, and lower glass transition temperatures and better low temperatures are achieved characteristic.

CN119403852APending Publication Date: 2025-02-07KURARAY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380048773.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-23
Filing Date
2023-06-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing hydrogenated styrene-type elastomers are difficult to maintain flexibility and rubber elasticity at low temperatures, and their glass transition temperature (Tg) is high, affecting the low temperature characteristics.

Method used

The structural unit derived from the conjugated diene compound of the polymer block (B) is set as a specific structural unit by the hydride of the block copolymer containing the polymer block (A) and the polymer block (B). , structural units including butadiene and isoprene without farnesene structural units, reduce the glass transition temperature of the block copolymer.

Benefits of technology

It realizes good flexibility, rubber elasticity and mechanical strength in lower temperature areas, reduces the glass transition temperature of block copolymers, improves the low temperature characteristics, and enhances the compatibility of oil components with hydrogenated block copolymers sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200347190000491
    Figure BDA0005200347190000491
  • Figure BDA0005200347190000492
    Figure BDA0005200347190000492
  • Figure BDA0005200347190000521
    Figure BDA0005200347190000521
Patent Text Reader

Abstract

Provided are: a hydrogenated block copolymer which has a low glass transition temperature and exhibits good flexibility, rubber elasticity and elongation characteristics even in a low-temperature region; a resin composition; a method for producing the hydrogenated block copolymer; and a hydrogenated block copolymer which contains a polymer block (A) and a polymer block (B), the polymer block (A) contains a structural unit derived from an aromatic vinyl compound, the polymer block (B) contains a structural unit derived from a conjugated diene compound, and the hydrogenated product of the block copolymer satisfies the following conditions (1)-(3). (1) The constituent units derived from the conjugated diene compound in the polymer block (B) have a constituent unit derived from butadiene and a constituent unit derived from isoprene, but do not have a constituent unit derived from farnesene. (2) The glass transition temperature of the hydrogenated product of the block copolymer is-50 DEG C or less. (3) the relationship of 5.8 x / 100,000-ygt is satisfied, where x is the weight-average molecular weight of the hydrogenated product of the block copolymer and y (DEG C) is the crystallization temperature of the hydrogenated product of the block copolymer; 17).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrogenated block copolymer, a resin composition, a gel composition, a cable filling material, a cable, a cosmetic, a lubricating oil, a lubricating grease and a method for producing the hydrogenated block copolymer. Background Art

[0002] Hydrogenated products of block copolymers including a polymer block (A) containing a structural unit derived from an aromatic vinyl compound and a polymer block (B) containing a structural unit derived from a conjugated diene compound (hereinafter also referred to as “hydrogenated block copolymers”) such as hydrogenated styrene-based elastomers are known.

[0003] There are cases where a hydrogenated styrene-based elastomer is required to exhibit flexibility even in a low temperature range.

[0004] It is known that hydrogenated styrene-based elastomers that contain a component having a low glass transition temperature (Tg) such as hydrogenated products of butadiene or isoprene (hereinafter sometimes referred to as "hydrogenated products") in a polymer block containing a structural unit derived from a conjugated diene compound can generally exhibit flexibility even at low temperatures.

[0005] If the Tg of the hydrogenated styrene-based elastomer can be lowered, the hydrogenated styrene-based elastomer can function as a rubber even in a lower temperature range, and thus can meet the demand for a rubber having better cold resistance.

[0006] Furthermore, it is considered that, in applications where impact resistance and thermal shock resistance are imparted to the resin by adding an elastomer, the Tg of the elastomer is set to a low temperature, thereby improving the physical properties of the resin such as impact resistance and thermal shock resistance in a low temperature range.

[0007] However, when a butadiene segment having 1,4-bonding in a polymer (hereinafter sometimes referred to as a "1,4-butadiene segment") is hydrogenated, the hydrogenated product of the 1,4-butadiene segment has an ethylene structure. Therefore, when a polymer block containing a structural unit derived from a conjugated diene compound is formed using only a 1,4-butadiene segment, the polymer block crystallizes and tends to lose flexibility.

[0008] Therefore, in conventional styrene-based elastomers, by including, for example, about 40% of a butadiene segment in which 1,2 bonds are formed in butadiene (hereinafter sometimes referred to as a "1,2-butadiene segment"), the degree of vinylization is increased, thereby preventing most of the polymer blocks containing structural units derived from conjugated diene compounds from crystallizing.

[0009] However, since the Tg of hydrogenated 1,2-polybutadiene is higher than that of hydrogenated 1,4-polybutadiene, a hydrogenated styrene elastomer containing a large amount of 1,2-butadiene segments has a problem in that its Tg becomes high and it is difficult to improve physical properties in a low temperature range.

[0010] Furthermore, it is believed that the chain structure of the hydrogenated form of the 1,4-butadiene segment will partially crystallize. If it has a long chain structure, the crystallization temperature becomes higher. Therefore, crystallization occurs at low temperatures, and the softness and impact resistance of the styrene elastomer are easily reduced. In addition, the mobility of the amorphous part located around the crystallized part is reduced due to the influence of the crystallized part showing low mobility. Therefore, it is believed that the crystallization of the butadiene segment is also related to the increase in the Tg of the hydrogenated block copolymer.

[0011] Therefore, there is a demand for improvement of properties in a lower temperature range by a novel method different from the conventional method of including a large amount of 1,2-butadiene segments.

[0012] It should be noted that a hydrogenated block copolymer containing a monomer unit derived from farnesene is known (see, for example, Patent Document 1). In Patent Document 1, vibration resistance, flexibility, rubber elasticity, and weather resistance are improved by the hydrogenated block copolymer.

[0013] Patent Document 2 describes that in order to obtain a hydrogenated block copolymer having a structure of styrene-hydrogenated (isoprene / butadiene)-styrene, tetrahydrofuran (THF) is added during the polymerization of isoprene and butadiene.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: International Publication No. 2013 / 183570

[0017] Patent Document 2: International Publication No. 2017 / 159800 Summary of the invention

[0018] Problems to be solved by the invention

[0019] The hydrogenated block copolymer of Patent Document 1 does not consider the improvement of properties such as flexibility, rubber elasticity, and mechanical strength in a temperature range of about -40°C or below -40°C. The hydrogenated block copolymer described in Patent Document 1 still has room for improvement in the above temperature range. In addition, if the amount of farnesene used increases, it is easy to cause cost increase and mechanical strength reduction. Therefore, a new method that does not require farnesene is sought.

[0020] In addition, the purpose of Patent Document 2 is to balance the softness and low-temperature impact resistance of a mixture obtained by adding a hydrogenated block copolymer to polypropylene. Therefore, when the hydrogenated block copolymer of Patent Document 2 is produced, a large amount of THF is added, and the vinyl bond content of the obtained hydrogenated block copolymer becomes large. As a result, the Tg of the hydrogenated block copolymer is about -40°C, which is relatively high, and there is still room for improvement in improving the characteristics at lower temperatures.

[0021] As described above, a hydrogenated styrene elastomer that exhibits excellent properties such as flexibility, rubber elasticity, and mechanical strength at lower temperatures is desired.

[0022] In addition, in order to further improve the thickening properties and other properties of the gel composition containing an oil component and a hydrogenated block copolymer used in grease, lubricating oils such as engine oil, cosmetics, etc., it is also desired to further improve the compatibility of the oil component and the hydrogenated block copolymer.

[0023] Therefore, an object of the present invention is to provide a hydrogenated block copolymer having a low glass transition temperature and exhibiting good flexibility, rubber elasticity and elongation characteristics even in a low temperature range, and a resin composition obtained using the hydrogenated block copolymer and a method for producing the hydrogenated block copolymer.

[0024] Another object of the present invention is to provide a gel composition which can further improve the compatibility between the oil component and the hydrogenated block copolymer and has excellent thickening properties.

[0025] Means used to solve problems

[0026] The present inventors have found that the above-mentioned problems can be solved by providing a hydrogenated product of a block copolymer comprising a polymer block (A) containing a structural unit derived from an aromatic vinyl compound and a polymer block (B) containing a structural unit derived from a conjugated diene compound, and by setting the structural unit of the polymer block (B) containing a structural unit derived from a conjugated diene compound to a specific structural unit, thereby completing the present invention.

[0027] The present invention relates to the following [1] to

[23] .

[0028] [1] A hydrogenated product of a block copolymer comprising a polymer block (A) and a polymer block (B), wherein the polymer block (A) contains a structural unit derived from an aromatic vinyl compound, and the polymer block (B) contains a structural unit derived from a conjugated diene compound, wherein the hydrogenated product of the block copolymer satisfies the following conditions (1) to (3).

[0029] (1) The structural unit derived from a conjugated diene compound in the polymer block (B) has a structural unit derived from butadiene and a structural unit derived from isoprene, and does not have a structural unit derived from farnesene.

[0030] (2) The glass transition temperature of the hydrogenated product of the block copolymer is -50°C or lower.

[0031] (3) When the weight average molecular weight of the hydrogenated product of the block copolymer is x and the crystallization temperature of the hydrogenated product of the block copolymer is y (° C.), the relationship of 5.8x / 100,000-y>17 is satisfied.

[0032] [2] The hydrogenated product of the block copolymer according to [1] above, wherein the content of the polymer block (A) in the hydrogenated product of the block copolymer is 5 to 70% by mass.

[0033] [3] The hydrogenated product of the block copolymer according to [2] above, wherein the content of the polymer block (A) in the hydrogenated product of the block copolymer is 8 to 33% by mass.

[0034] [4] The hydrogenated product of the block copolymer according to any one of [1] to [3] above, wherein the amount of vinyl bonds in the polymer block (B) is 25 mol% or less.

[0035] [5] The hydrogenated product of the block copolymer according to [4] above, wherein the amount of vinyl bonds in the polymer block (B) is 18 mol% or less.

[0036] [6] The hydrogenated product of the block copolymer according to any one of [1] to [5] above, wherein the content of the structural unit derived from butadiene in the polymer block (B) is 10 to 90 mol%.

[0037] [7] The hydrogenated product of the block copolymer according to [6] above, wherein the content of the structural unit derived from butadiene in the polymer block (B) is 15 to 70 mol%.

[0038] [8] The hydrogenated product of the block copolymer according to [6] above, wherein the content of the structural unit derived from butadiene in the polymer block (B) is 30 to 85 mol%.

[0039] [9] The hydrogenated product of the block copolymer according to any one of [1] to [8] above, wherein the heat of crystallization of the hydrogenated product of the block copolymer is 20 J / g or less.

[0040]

[10] The hydrogenated product of the block copolymer according to any one of [1] to [9] above, wherein the weight average molecular weight of the hydrogenated product of the block copolymer is 30,000 to 500,000.

[0041]

[11] The hydrogenated product of the block copolymer according to any one of [1] to

[10] above, wherein the hydrogenation rate of the polymer block (B) is 90 mol% or more.

[0042]

[12] The hydrogenated product of the block copolymer according to any one of [1] to

[11] above, which further satisfies the following condition (4).

[0043] (4) Decoupling through anti-gating 13 The chain ratio of 1,4-bonds of hydrogenated butadiene represented by the ratio of the peak appearing at 29.2 ppm among the peaks derived from 1,4-bonds of hydrogenated butadiene obtained by C-NMR measurement was less than 50%.

[0044]

[13] The hydrogenated block copolymer according to any one of [1] to

[12] above, wherein the tensile elongation at break measured in accordance with JIS K6251 (2017) is 300% or more.

[0045]

[14] The hydrogenated block copolymer according to any one of [1] to

[13] above, wherein the shear storage modulus G′ at -40°C measured by a complex shear viscosity test at a frequency of 1 Hz in accordance with JIS K7244-10 (2005) is 200 MPa or less.

[0046]

[15] A resin composition comprising, as component (a), a hydrogenated product of the block copolymer described in any one of [1] to

[14] above, and

[0047] As component (b), at least one oil component selected from mineral oil, vegetable oil and ethylene / α-olefin copolymer oligomer is contained,

[0048] The content ratio (a) / (b) of the component (a) and the component (b) is 1 / 99 to 99 / 1 in terms of mass ratio.

[0049]

[16] A resin composition comprising, as component (a), a hydrogenated product of the block copolymer described in any one of [1] to

[14] above; and

[0050] As component (c), at least one selected from polyethylene, polypropylene, styrene resins, polyphenylene ether, polyester resins, polycarbonate, polyacetal, polyamide, polyarylene sulfide, polyarylate, polyimide, polyetheretherketone and liquid crystal polyester is contained,

[0051] The content ratio (a) / (c) of the component (a) and the component (c) is 1 / 99 to 99 / 1 in terms of mass ratio.

[0052]

[17] A gel composition comprising a base oil (β) and a hydrogenated product of the block copolymer according to any one of claims 1 to 14 as a component (α).

[0053]

[18] A cable filling material comprising the gel composition described in

[17] above.

[0054]

[19] A cable comprising the gel composition described in

[17] above.

[0055]

[20] A cosmetic comprising the gel composition described in

[17] above.

[0056]

[21] A lubricating oil comprising the gel composition described in

[17] above.

[0057]

[22] A grease comprising the gel composition described in

[17] above.

[0058]

[23] A method for producing a hydrogenated block copolymer according to any one of [1] to

[14] , comprising the following steps:

[0059] A first step of performing a polymerization reaction using a polymerization initiator and at least an aromatic vinyl compound, butadiene and isoprene as monomers to obtain a block copolymer including a polymer block (A) containing a structural unit derived from the aromatic vinyl compound and a polymer block (B) containing a structural unit derived from butadiene and a structural unit derived from isoprene; and

[0060] The second step is to hydrogenate the block copolymer.

[0061] In the first step, at least one of the following elements (i) to (vi) is performed.

[0062] (i) The average feed rate when feeding the butadiene and isoprene to the reaction system is set to 50 kg / h / mol or less.

[0063] (ii) The polymerization temperature is set to 55 to 80°C.

[0064] (iii) A vinylating agent is added to the reaction system in an amount of 0.3% by mass or less based on the total mass of the raw material compounds.

[0065] (iv) The time for feeding the butadiene and isoprene into the reaction system is set to 2.5 hours or longer.

[0066] (v) When the amount of the polymerization initiator charged is P (mol) and the amount of the unreacted conjugated diene monomer is Q (mol), Q / P during polymerization of the polymer block (B) is 100 or less.

[0067] (vi) The mass ratio of the butadiene and isoprene when the butadiene and isoprene are fed into the reaction system varies depending on the timing of feeding into the reaction system.

[0068] Effects of the Invention

[0069] According to the present invention, there are provided a hydrogenated block copolymer having a low glass transition temperature and exhibiting good flexibility, rubber elasticity and elongation characteristics even in a low temperature range, a resin composition obtained using the hydrogenated block copolymer, and a method for producing the hydrogenated block copolymer.

[0070] In addition, according to the present invention, the compatibility between the oil component and the hydrogenated block copolymer can be further improved, and a gel composition having excellent thickening properties can be provided. DETAILED DESCRIPTION

[0071] Hereinafter, embodiments of the present invention will be described.

[0072] The present invention also includes any form obtained by arbitrarily selecting or arbitrarily combining the matters described in this specification.

[0073] In the present specification, provisions considered to be preferred can be arbitrarily selected, and it can be said that a combination of provisions considered to be preferred is more preferred.

[0074] In this specification, the description "XX to YY" means "XX or more and YY or less".

[0075] In this specification, regarding the preferred numerical range (e.g., the range of content, etc.), the lower limit and upper limit described in stages can be combined independently. For example, according to the description of "preferably 10 to 90, more preferably 30 to 60", the "preferable lower limit (10)" and the "more preferably upper limit (60)" can also be combined to "10 to 60".

[0076] [Hydrogenated block copolymer]

[0077] The hydrogenated product of the block copolymer according to the first embodiment of the present invention comprises a polymer block (A) and a polymer block (B), wherein the polymer block (A) contains a structural unit derived from an aromatic vinyl compound, and the polymer block (B) contains a structural unit derived from a conjugated diene compound, and the hydrogenated product of the block copolymer satisfies the following conditions (1) to (3).

[0078] (1) The structural unit derived from a conjugated diene compound in the polymer block (B) has a structural unit derived from butadiene and a structural unit derived from isoprene, and does not have a structural unit derived from farnesene.

[0079] (2) The glass transition temperature of the hydrogenated product of the block copolymer is -50°C or lower.

[0080] (3) When the weight average molecular weight of the hydrogenated product of the block copolymer is x and the crystallization temperature of the hydrogenated product of the block copolymer is y (° C.), the relationship of 5.8x / 100,000-y>17 is satisfied.

[0081] As specified in condition (1), by using butadiene and isoprene as monomers for constituting the polymer block (B), the continuous bonding of structural units derived from butadiene is suppressed, and the crystallization of the butadiene segment is easily prevented. In addition, by not using farnesene as the above-mentioned monomer, the hydrogenated product of the block copolymer can be made low-cost, and it is also easy to prevent the mechanical strength of the hydrogenated product of the block copolymer from being reduced.

[0082] However, the present inventors have made intensive studies and found that, in the hydrogenated products of the conventionally proposed block copolymers, the structural units derived from butadiene and the structural units derived from isoprene are concentrated in the polymer block (B), and discovered that the characteristics in the low temperature region can be improved by reducing this concentration.

[0083] Furthermore, the inventors of the present invention have further conducted research and found that, as specified in the above condition (3), if the weight average molecular weight x of the hydrogenated block copolymer and the crystallization temperature y (°C) of the hydrogenated block copolymer satisfy the relationship of 5.8x / 100,000-y>17, the unbalanced presence of structural units derived from butadiene can be suppressed. The amount of polymerization initiator used in the manufacture of the hydrogenated block copolymer with a large weight average molecular weight is usually small, so the amount of conjugated diene increases relative to the amount of polymerization initiator, and the unbalanced presence of structural units derived from butadiene is likely to occur. However, if the randomness of the structural units derived from butadiene and the structural units derived from isoprene is increased, the crystallization of the polymer block (B) is easily suppressed. Therefore, it can be considered that if the unbalanced presence of structural units derived from butadiene is suppressed, the above condition (3) is satisfied.

[0084] If the molecular weight of the block copolymer is increased in order to cope with various purposes, the molecular weight of the polymer block, i.e., the polymer block (B) other than the two ends in the block copolymer, also becomes larger. Therefore, if the hydrogenated block copolymer is manufactured using the previous manufacturing conditions, there is a tendency for the ethylene chain length to become longer (i.e., the tendency for randomness to decrease) based on the chain of the structural unit derived from butadiene. As a result, there is a tendency for the crystallization temperature (Tc) of the hydrogenated block copolymer to also become higher. Thus, by removing the influence of the molecular weight and using Tc, the above-mentioned condition (3) is presented to reflect the polymer block (B) having good low temperature characteristics. The hydrogenated block copolymer satisfying condition (3) can be obtained according to the steps described in, for example, "the method for manufacturing hydrogenated block copolymers" described later.

[0085] Thus, by satisfying the above conditions (1) and (3), it is easy to satisfy the condition specified in the above condition (2) in addition to satisfying the conditions (1) and (3), and as a result, various properties such as flexibility, rebound resilience, and mechanical strength in a low temperature range can be improved. In addition, it is believed that when the above hydrogenated block copolymer is used together with an oil component to prepare a gel composition, the compatibility of the hydrogenated block copolymer and the oil component can be further improved, and when the gel composition is used as a gel composition for grease, cable filling material, cosmetics, etc., good thickening properties can be obtained.

[0086] From the viewpoint of more easily satisfying the above condition (2), in the above condition (3), the value of "5.8x / 100,000-y" is preferably 18 or more, more preferably 19 or more, further preferably 20 or more, further preferably 25 or more, and particularly preferably 30 or more. The upper limit of the value of "5.8x / 100,000-y" is not particularly limited, but is usually 200 or less, may be 100 or less, or may be 50 or less.

[0087] It should be noted that in this specification, the Tg of the hydrogenated block copolymer is measured using a differential scanning calorimeter (DSC). Specifically, in a DSC curve prepared using DSC, the temperature at which the baseline shifts is set to Tg. In more detail, the Tg of the hydrogenated block copolymer is measured according to the method described in the examples.

[0088] The hydrogenated product of the block copolymer preferably further satisfies the following condition (4) from the viewpoint of reducing the imbalance of the structural units derived from butadiene and the structural units derived from isoprene in the polymer block (B) and increasing the randomness of the structural units derived from butadiene and the structural units derived from isoprene.

[0089] (4) Decoupling through anti-gating 13The chain ratio of 1,4-bonds of hydrogenated butadiene represented by the ratio of the peak appearing at 29.2 ppm among the peaks derived from 1,4-bonds of hydrogenated butadiene obtained by C-NMR measurement was less than 50%.

[0090] The chain rate of the 1,4-bond of hydrogenated butadiene is: 13 The ratio of the peak appearing at 29.2 ppm obtained by C-NMR measurement to all peaks derived from 1,4-bonds of hydrogenated butadiene. Specifically, the chain ratio of 1,4-bonds of the hydrogenated butadiene is measured by the method described in Examples.

[0091] In the above condition (4), from the viewpoint of increasing the randomness of the structural units derived from butadiene and the structural units derived from isoprene, the chain rate of 1,4-bonds of hydrogenated butadiene is preferably 49% or less, more preferably 48% or less, further preferably 45% or less, and further preferably 40% or less. The lower limit is not particularly limited, but from the viewpoint of ease of production, it is, for example, 1% or more. In other words, the chain rate of 1,4-bonds of the above hydrogenated butadiene is preferably 1% or more and less than 50%.

[0092] In addition, the hydrogenated product of the block copolymer according to the second embodiment of the present invention comprises a polymer block (A) and a polymer block (B), wherein the polymer block (A) contains a structural unit derived from an aromatic vinyl compound, and the polymer block (B) contains a structural unit derived from a conjugated diene compound, and the hydrogenated product of the block copolymer satisfies the following conditions (I) to (III).

[0093] The structural unit derived from a conjugated diene compound in the (I) polymer block (B) has a structural unit derived from butadiene and a structural unit derived from isoprene, and preferably does not have a structural unit derived from farnesene.

[0094] (II) The glass transition temperature of the hydrogenated product of the block copolymer is -50°C or lower.

[0095] (III) Decoupling by anti-gating 13 The chain ratio of 1,4-bonds of hydrogenated butadiene represented by the ratio of the peak appearing at 29.2 ppm among the peaks derived from 1,4-bonds of hydrogenated butadiene obtained by C-NMR measurement was less than 50%.

[0096] As specified in condition (III) above, by decoupling the 13Among the peaks derived from 1,4-bonds of hydrogenated butadiene obtained by C-NMR measurement, the chain ratio of 1,4-bonds of hydrogenated butadiene represented by the ratio of the peak appearing at 29.2 ppm is less than a specific ratio, so that the unbalanced presence of structural units derived from butadiene is suppressed, the randomness of structural units derived from butadiene and structural units derived from isoprene is improved, and the crystallization of the polymer block (B) is easily suppressed.

[0097] Regarding condition (I), similarly to condition (1), by using butadiene and isoprene as monomers for constituting the polymer block (B), continuous bonding of structural units derived from butadiene is suppressed, and crystallization of the butadiene segment is easily prevented.

[0098] Furthermore, by satisfying the above conditions (I) and (III), it is easy to satisfy the conditions specified in the above condition (II) in addition to satisfying the conditions (I) and (III), and as a result, various properties such as flexibility, rebound resilience, and mechanical strength in a low temperature range can be improved. In addition, it is believed that when the above hydrogenated block copolymer is used together with an oil component to prepare a gel composition, the compatibility of the hydrogenated block copolymer and the oil component can be further improved, and when the gel composition is used as a gel composition for grease, cable filling material, cosmetics, etc., good thickening properties can be obtained.

[0099] Hereinafter, each component constituting the hydrogenated product of the block copolymer will be described. It should be noted that, unless otherwise specified, the following description applies to both the first embodiment and the second embodiment described above. In addition, the first embodiment and the second embodiment described above are sometimes collectively referred to as "this embodiment".

[0100] <Block copolymer>

[0101] The hydrogenated product of the block copolymer is obtained by hydrogenating the block copolymer.

[0102] The hydrogenated product of the block copolymer according to the embodiment of the present invention includes a polymer block (A) containing a structural unit derived from an aromatic vinyl compound and a polymer block (B) containing a structural unit derived from a conjugated diene compound.

[0103] Furthermore, as defined in the above conditions (1) and (I), the structural unit derived from the conjugated diene compound of the polymer block (B) includes a structural unit derived from butadiene and a structural unit derived from isoprene. The polymer block (B) will be described in detail later.

[0104] In addition, as specified in the above conditions (2) and (II), the Tg of the hydrogenated block copolymer is -50°C or less. From the viewpoint of easily ensuring impact resistance and rubber elasticity at lower temperatures, the Tg of the hydrogenated block copolymer is preferably -53°C or less, more preferably -55°C or less, further preferably -57°C or less, and further preferably -59°C or less. The lower limit of the Tg of the hydrogenated block copolymer is not particularly limited, and for example, from the viewpoint of ease of manufacture, it is -80°C. In other words, the Tg of the hydrogenated block copolymer is preferably -80 to -50°C.

[0105] The Tg of the hydrogenated block copolymer can be adjusted to the above range by, for example, reducing the content of structural units derived from butadiene in the polymer block (B) of the hydrogenated block copolymer and suppressing crystallization of hydrogenated butadiene.

[0106] (Polymer block (A))

[0107] The polymer block (A) contains a structural unit derived from an aromatic vinyl compound (hereinafter sometimes referred to as "aromatic vinyl compound unit"). From the viewpoint of mechanical properties, the content of the structural unit is preferably more than 70 mol%, more preferably 80 mol% or more, further preferably 85 mol% or more, further preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be substantially 100 mol%. In other words, the content of the aromatic vinyl compound unit in the polymer block (A) is preferably more than 70 mol% and not more than 100 mol%.

[0108] Examples of the aromatic vinyl compound include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, β-methylstyrene, 2,6-dimethylstyrene, 2,4-dimethylstyrene, α-methyl-o-methylstyrene, α-methyl-m-methylstyrene, α-methyl-p-methylstyrene, β-methyl-o-methylstyrene, β-methyl-m-methylstyrene, β-methyl-p-methylstyrene, 2,4,6-trimethylstyrene, α-methyl-2,6-dimethylstyrene, α-methyl-2,4-dimethylstyrene, β-methyl-2,6-dimethylstyrene, β-methyl-2,4-dimethylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,6-dichlorostyrene, Olefins, 2,4-dichlorostyrene, α-chloro-o-chlorostyrene, α-chloro-m-chlorostyrene, α-chloro-p-chlorostyrene, β-chloro-o-chlorostyrene, β-chloro-m-chlorostyrene, β-chloro-p-chlorostyrene, 2,4,6-trichlorostyrene, α-chloro-2,6-dichlorostyrene, α-chloro-2,4-dichlorostyrene, β-chloro-2,6-dichlorostyrene, β-chloro-2,4-dichlorostyrene, o-tert-butylstyrene, m-tert-butylstyrene, p-tert-butylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-chloromethylstyrene, m-chloromethylstyrene, p-chloromethylstyrene, o-bromomethylstyrene, m-bromomethylstyrene, p-bromomethylstyrene, styrene derivatives substituted with silyl groups, indene, vinylnaphthalene, etc. These aromatic vinyl compounds can be used alone or in combination. Among them, from the viewpoint of manufacturing cost and physical property balance, styrene, α-methylstyrene, p-methylstyrene and mixtures thereof are preferred, and styrene is more preferred.

[0109] As long as the purpose and effect of the present invention are not impaired, the polymer block (A) may contain structural units derived from other unsaturated monomers other than aromatic vinyl compounds (hereinafter sometimes referred to as "other unsaturated monomer units") at a ratio of less than 30 mol%. Examples of the other unsaturated monomers include butadiene, isoprene, 2,3-dimethylbutadiene, 1,3-pentadiene, 1,3-hexadiene, isobutylene, methyl methacrylate, methyl vinyl ether, N-vinyl carbazole, β-pinene, 8,9-menthene, dipentene, methylene norbornene, 2-methylenetetrahydrofuran, and the like. The bonding form when the polymer block (A) contains the other unsaturated monomer units is not particularly limited, and may be any of random and tapered.

[0110] The content of the structural unit derived from the other unsaturated monomer in the polymer block (A) is preferably 10 mol% or less, more preferably 5 mol% or less, and even more preferably 0 mol%.

[0111] The hydrogenated block copolymer only needs to have at least one of the polymer blocks (A). When the hydrogenated block copolymer has two or more polymer blocks (A), these polymer blocks (A) may be the same or different. It should be noted that in this specification, "different polymer blocks" means that at least one of the monomer units constituting the polymer blocks, the weight-average molecular weight, the stereoregularity, the ratio of each monomer unit when there are multiple monomer units, and the copolymerization form (random, gradient, block) is different.

[0112] From the viewpoint of easily ensuring rubber elasticity, the hydrogenated block copolymer preferably has two polymer blocks (A).

[0113] The weight average molecular weight (Mw) of the polymer block (A) is not particularly limited. Among the polymer blocks (A) possessed by the hydrogenated block copolymer, the weight average molecular weight of at least one polymer block (A) is preferably 3,000 to 60,000, more preferably 6,000 to 55,000, further preferably 7,000 to 50,000, further preferably 7,500 to 40,000, particularly preferably 8,000 to 35,000, and most preferably 8,000 to 30,000, from the viewpoint of mechanical strength and moldability. From the viewpoint of fluidity and impact resistance, the weight average molecular weight of at least one polymer block (A) is preferably 3,000 to 60,000, more preferably 3,500 to 15,000, further preferably 4,000 to 10,000, further preferably 4,200 to 9,000, particularly preferably 4,300 to 8,000, and most preferably 4,500 to 7,000.

[0114] It should be noted that the "weight average molecular weight" described in this specification and claims is the weight average molecular weight calculated by standard polystyrene conversion determined by gel permeation chromatography (GPC), and the detailed determination method can follow the method described in the examples. In the case of the triblock copolymer having the above-mentioned A1-B-A2 structure, the total weight average molecular weight of the polymer blocks "A1" and "A2" is calculated based on the weight average molecular weight of the block copolymer and the weight average molecular weight of the block copolymer determined by GPC. 1 The total content of polymer blocks "A1" and "A2" confirmed by H-NMR measurement is calculated, and the weight average molecular weight of the deactivated initial polymer block "A1" is calculated by GPC measurement and subtracted to obtain the weight average molecular weight of the polymer block "A2".

[0115] From the viewpoint of easily ensuring impact resistance and rubber elasticity at lower temperatures, the content of the polymer block (A) in the hydrogenated block copolymer (the total content of the polymer blocks (A) when there are a plurality of polymer blocks (A)) is preferably 5 to 70% by mass, more preferably 8 to 33% by mass, further preferably 10 to 25% by mass, and further preferably 15 to 22% by mass. In addition, from the viewpoint of mechanical properties, it is preferably 5 to 70% by mass, more preferably 15 to 50% by mass, further preferably 20 to 40% by mass, and further preferably 25 to 35% by mass.

[0116] It should be noted that the content of the polymer block (A) in the hydrogenated block copolymer is determined by 1 More specifically, the values ​​obtained by H-NMR measurement were measured according to the method described in Examples.

[0117] (Polymer block (B))

[0118] In the hydrogenated product of the block copolymer described in the first embodiment, the polymer block (B) contains a structural unit derived from a conjugated diene compound (hereinafter sometimes simply referred to as a "conjugated diene compound unit"), and the conjugated diene compound unit has a structural unit derived from butadiene and a structural unit derived from isoprene, and does not have a structural unit derived from farnesene.

[0119] The Tg of polyethylene having a structure equivalent to that obtained by hydrogenating a 1,4-butadiene segment is about -120° C. Therefore, it is expected that a hydrogenated block copolymer with a low Tg can be obtained if hydrogenated butadiene is used as the polymer block (B) containing a structural unit derived from a conjugated diene compound and crystallization is further prevented.

[0120] Therefore, by using isoprene as a monomer constituting the polymer block (B), continuous bonding of structural units derived from butadiene is suppressed, and crystallization of butadiene is easily prevented. As a result, crystallization of the polymer block (B) is easily suppressed.

[0121] However, according to the research of the present inventors, it is known that if the structural units derived from butadiene and the structural units derived from isoprene are concentrated in the polymer block (B), the bonding units derived from butadiene are likely to be continuously bonded, and the polymer block (B) is likely to crystallize. In addition, the results show that the characteristics in the low temperature range cannot be fully improved.

[0122] Therefore, as specified in the above condition (3), if the weight average molecular weight x of the hydrogenated product of the block copolymer and the crystallization temperature y (°C) of the hydrogenated product of the block copolymer satisfy a specific relationship, the uneven presence of the structural units derived from butadiene is suppressed, the randomness of the structural units derived from butadiene and the structural units derived from isoprene is improved, and the crystallization of the polymer block (B) is easily suppressed.

[0123] In the hydrogenated product of the block copolymer according to the second embodiment, the polymer block (B) contains a conjugated diene compound unit having a structural unit derived from butadiene and a structural unit derived from isoprene, and preferably does not have a structural unit derived from farnesene.

[0124] Regarding the hydrogenated product of the block copolymer according to the second embodiment, as specified in the condition (III), by setting the chain ratio of 1,4-bonds of hydrogenated butadiene in the hydrogenated product of the block copolymer to a specific range, the unbalanced presence of structural units derived from butadiene is suppressed, the randomness of structural units derived from butadiene and structural units derived from isoprene is improved, and the crystallization of the polymer block (B) is easily suppressed.

[0125] In the hydrogenated product of the block copolymer described in the first embodiment, the polymer block (B) may or may not contain structural units derived from conjugated diene compounds other than butadiene, isoprene and β-farnesene, as long as the purpose and effect of the present invention are not hindered. From the viewpoint of easily obtaining the target performance, it is desirable not to contain structural units derived from conjugated diene compounds other than butadiene, isoprene and β-farnesene (in other words, as conjugated diene compound units, only structural units derived from butadiene and isoprene are included).

[0126] From the viewpoint of flexibility and rubber elasticity, the total content of the conjugated diene compound units in the polymer block (B) is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more. The upper limit is not particularly limited and can be set to 100% by mass. In other words, the total content of the conjugated diene compound units in the polymer block (B) is preferably 60 to 100% by mass.

[0127] It should be noted that the total content of the conjugated diene compound units in the polymer block (B) is preferably 30 mol% or more, more preferably 50 mol% or more, further preferably 65 mol% or more, further preferably 80 mol% or more, particularly preferably 90 mol% or more, and most preferably substantially 100 mol%. In other words, the total content of the conjugated diene compound units in the polymer block (B) is preferably 30 to 100 mol%.

[0128] In the hydrogenated product of the block copolymer described in the first embodiment, from the viewpoint of suppressing the crystallization of the polymer block (B) and improving the low temperature characteristics, the content of the structural unit derived from butadiene in the polymer block (B) is preferably 10 to 90 mol%, more preferably 15 to 70 mol%, and further preferably 20 to 60 mol%. In addition, from the viewpoint of increasing the content of butadiene and increasing the entanglement between the hydrogenated block copolymers to improve the strength, it is preferably 10 to 90 mol%, more preferably 30 to 85 mol%, further preferably 40 to 80 mol%, and particularly preferably 45 to 75 mol%.

[0129] In the hydrogenated product of the block copolymer described in the first embodiment, the mixing ratio [butadiene / isoprene] (mass ratio) of the conjugated diene compound is not particularly limited as long as the effect of the present invention is not impaired, and is preferably 10 / 90 to 90 / 10, more preferably 20 / 80 to 80 / 20, and further preferably 30 / 70 to 70 / 30. It should be noted that if the mixing ratio [butadiene / isoprene] is expressed in terms of molar ratio, it is preferably 6 / 94 to 96 / 4, more preferably 12 / 88 to 92 / 8, further preferably 24 / 76 to 83 / 17, and particularly preferably 35 / 65 to 75 / 25.

[0130] In the hydrogenated product of the block copolymer described in the second embodiment, the polymer block (B) may or may not contain a structural unit derived from a conjugated diene compound other than butadiene and isoprene, as long as the purpose and effect of the present invention are not impaired. Examples of the conjugated diene compound other than butadiene and isoprene include β-farnesene and myrcene.

[0131] From the viewpoint of easily obtaining the target performance, it is desirable that the polymer block (B) does not contain a structural unit derived from a conjugated diene compound other than butadiene and isoprene. From this viewpoint and the viewpoint of cost, it is desirable that the polymer block (B) does not contain a structural unit derived from β-farnesene.

[0132] In the hydrogenated product of the block copolymer according to the second embodiment, suitable numerical ranges for the total content of the conjugated diene compound units in the polymer block (B), the content of the structural units derived from butadiene in the polymer block (B), and the mixing ratio of the conjugated diene compounds [butadiene / isoprene] (mass ratio, molar ratio) are the same as those described for the polymer block (B) of the hydrogenated product of the block copolymer according to the first embodiment.

[0133] In addition, as long as the purpose and effect of the present invention are not hindered, in the hydrogenated block copolymer described in the first embodiment and the second embodiment, the polymer block (B) may contain structural units derived from other polymerizable monomers other than the conjugated diene compound. In this case, in the polymer block (B), the content of structural units derived from other polymerizable monomers other than the conjugated diene compound is preferably 70 mol% or less, more preferably 50 mol% or less, further preferably 35 mol% or less, and particularly preferably 20 mol% or less. The lower limit of the content of structural units derived from other polymerizable monomers other than the conjugated diene compound is not particularly limited, and may be 0 mol%, 5 mol%, or 10 mol%. In other words, the content of structural units derived from polymerizable monomers other than the conjugated diene compound in the polymer block (B) is preferably 0 to 70 mol%.

[0134] As the other polymerizable monomer, preferably, for example, at least one compound selected from aromatic vinyl compounds such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, vinylnaphthalene and vinylanthracene, and methyl methacrylate, methyl vinyl ether, N-vinylcarbazole, β-pinene, 8,9-p-menthene, dipentene, methylenenorbornene, 2-methylenetetrahydrofuran, 1,3-cyclopentadiene, 1,3-cyclohexadiene, 1,3-cycloheptadiene, 1,3-cyclooctadiene, etc. Among them, styrene, α-methylstyrene and p-methylstyrene are more preferred, and styrene is further preferred.

[0135] When the polymer block (B) contains a structural unit derived from a polymerizable monomer other than the conjugated diene compound, the bonding form is not particularly limited and may be random or tapered, but is preferably random.

[0136] In addition, the hydrogenated block copolymer described in the first embodiment and the second embodiment above only needs to have at least one polymer block (B). In the case where the hydrogenated block copolymer has two or more polymer blocks (B), these polymer blocks (B) may be the same or different. In the case where the polymer block (B) has two or more structural units, their bonding forms may include random, tapered, completely alternating, partially block-shaped, block, or a combination of two or more thereof. From the viewpoint of easily ensuring impact resistance and rubber elasticity at low temperatures, the polymer block (B) in the hydrogenated block copolymer is preferably 3 or less, more preferably 2 or less. When the hydrogenated block copolymer is used for purposes that emphasize rubber elasticity, the polymer block (B) in the hydrogenated block copolymer is further preferably 1. It should be noted that in the case where the hydrogenated block copolymer has two or more polymer blocks (B), these polymer blocks (B) may be the same or different.

[0137] As long as the purpose and effect of the present invention are not impaired, the bonding form of the conjugated diene compound is not particularly limited. For example, as the bonding form of butadiene and isoprene, in the case of butadiene, 1,2-bonding and 1,4-bonding can be adopted, and in the case of isoprene, 1,2-bonding, 3,4-bonding and 1,4-bonding can be adopted. There may be only one of these bonding forms, or there may be two or more.

[0138] From the viewpoint of easily ensuring impact resistance and rubber elasticity at lower temperatures, the content of the polymer block (B) in the hydrogenated block copolymer described in the first embodiment and the second embodiment (when there are a plurality of polymer blocks (B), the total content thereof) is preferably 30 to 95% by mass, more preferably 67 to 92% by mass, further preferably 75 to 90% by mass, and further preferably 78 to 85% by mass. In addition, from the viewpoint of mechanical properties, it is preferably 30 to 95% by mass, more preferably 50 to 85% by mass, further preferably 60 to 80% by mass, and further preferably 65 to 75% by mass.

[0139] It should be noted that the content of the polymer block (B) in the hydrogenated block copolymer is determined by 1 More specifically, the values ​​obtained by H-NMR measurement were measured according to the method described in Examples.

[0140] (Vinyl Bond Amount of Polymer Block (B))

[0141] Among the bonding forms of the structural units constituting the polymer block (B), 1,2-bonds derived from butadiene and 1,2-bonds and 3,4-bonds derived from isoprene are referred to as vinyl bonds, and the content of the vinyl bond units is referred to as the vinyl bond amount. The vinyl bond amount of the polymer block (B) refers to the ratio of the 3,4-bond units and 1,2-bond units in the isoprene structural units and the 1,2-bond units in the butadiene structural units to the total structural units derived from butadiene and isoprene.

[0142] In the hydrogenated block copolymers described in the first embodiment and the second embodiment, from the viewpoint of reducing Tg, the total amount of vinyl bonds in the polymer block (B) is preferably 25 mol% or less, more preferably 20 mol% or less, further preferably 18 mol% or less, further preferably 16 mol% or less, and particularly preferably 14 mol% or less. In addition, from the viewpoint of inhibiting crystallization, it is preferably 3 mol% or more, more preferably 5 mol% or more, further preferably 8 mol% or more, and particularly preferably 10 mol% or more. In other words, the amount of vinyl bonds in the polymer block (B) is preferably 3 to 25 mol%. Here, the amount of vinyl bonds is determined by the method described in the examples and by 1 The value was calculated by H-NMR measurement.

[0143] From the viewpoint of impact resistance at low temperature, the total weight average molecular weight of the polymer block (B) of the hydrogenated block copolymer described in the first embodiment and the second embodiment is preferably 15,000 to 800,000, more preferably 20,000 to 200,000, further preferably 30,000 to 150,000, particularly preferably 50,000 to 130,000, and most preferably 70,000 to 100,000 before hydrogenation. In addition, from the viewpoint of rubber elasticity and mechanical properties, the total weight average molecular weight of the polymer block (B) is preferably 15,000 to 800,000, more preferably 50,000 to 600,000, further preferably 60,000 to 400,000, particularly preferably 65,000 to 350,000, and most preferably 70,000 to 300,000 before hydrogenation.

[0144] In the hydrogenated block copolymer, it is desirable that the polymer block (B) does not contain a structural unit derived from an aromatic vinyl compound. If the polymer block (B) contains a structural unit derived from an aromatic vinyl compound, the impact resistance and rubber elasticity at low temperatures may be reduced.

[0145] (Bonding method of polymer block (A) and polymer block (B))

[0146] For the above-mentioned hydrogenated block copolymer, as long as the polymer block (A) and the polymer block (B) are bonded, the bonding form is not limited, and can be any one of the bonding modes obtained by combining linear, branched, radial or two or more thereof. Among them, the bonding form of polymer block (A) and polymer block (B) is preferably linear, as an example, when polymer block (A) is shown as "A" and polymer block (B) is shown as "B", diblock copolymers shown in AB, triblock copolymers shown in ABA or BAB, tetrablock copolymers shown in ABAB, pentablock copolymers shown in ABABA or BABAB, (AB) nX type copolymers (X represents a coupling agent residue, and n represents an integer greater than 3) and the like can be listed. Among them, preferably a linear triblock copolymer or a diblock copolymer, from the viewpoints of flexibility, ease of manufacture, etc., preferably a triblock copolymer of ABA type is used.

[0147] Here, in this specification, when the same type of polymer blocks are bonded into a linear shape by means of a bifunctional coupling agent, etc., the bonded polymer blocks are treated as a single polymer block as a whole. According to this point, including the above-mentioned examples, the polymer block that should be strictly expressed as YXY (X represents a coupling residue) is shown as Y as a whole except for the case where it is necessary to distinguish it from the independent polymer block Y. In this specification, such a polymer block containing a coupling agent residue is treated as above, so, for example, a block copolymer containing a coupling agent residue and should be strictly expressed as ABXBA (X represents a coupling agent residue) is expressed as ABA and treated as an example of a triblock copolymer.

[0148] The hydrogenation rate of the polymer block (B) is preferably 90 mol% or more. In other words, 90 mol% or more of the carbon-carbon double bonds of the polymer block (B) are preferably hydrogenated. Here, the hydrogenation rate of the polymer block (B) is based on the amount of double bonds before hydrogenation.

[0149] If the hydrogenation rate of the polymer block (B) is high, the heat resistance and weather resistance are excellent. From the same viewpoint, the hydrogenation rate of the polymer block (B) is more preferably 91 mol% or more, more preferably 92 mol% or more, further preferably 93 mol% or more, and particularly preferably 95 mol% or more. The upper limit of the hydrogenation rate is not particularly limited, and the upper limit can be substantially 100 mol%, 99.8 mol%, 99.5 mol%, or 99 mol%. In other words, the hydrogenation rate of the polymer block (B) is preferably 90 to 100 mol%.

[0150] It should be noted that the above hydrogenation rate is obtained by 1The value obtained by determining the content of carbon-carbon double bonds in the structural unit derived from the conjugated diene compound in the hydrogenated polymer block (B) by H-NMR measurement is, more specifically, a value measured by the method described in Examples.

[0151] (Contents of polymer block (A) and polymer block (B))

[0152] From the viewpoint of easily exhibiting the target performance, the total content of the polymer block (A) and the polymer block (B) in the hydrogenated block copolymer is preferably 95% by mass or more, more preferably 98% by mass or more, further preferably 99% by mass or more, and may be 100% by mass.

[0153] It should be noted that the hydrogenated product of the block copolymer preferably consists of only the block copolymer (A) and the block copolymer (B), and may contain unavoidable impurity components.

[0154] (Weight average molecular weight (Mw) of hydrogenated block copolymer)

[0155] The weight average molecular weight (Mw) of the hydrogenated product of the block copolymer obtained by standard polystyrene conversion based on gel permeation chromatography is not particularly limited, but is preferably 30,000 to 500,000 from the viewpoint of balance between heat resistance and moldability. From the viewpoint of heat resistance, the lower limit of the weight average molecular weight (Mw) of the hydrogenated product of the block copolymer is more preferably 60,000 or more, more preferably 70,000 or more, particularly preferably 80,000 or more, more particularly preferably 85,000 or more, and most preferably 90,000 or more. In addition, in the case of attaching importance to moldability, the upper limit of the weight average molecular weight (Mw) of the hydrogenated product of the block copolymer is more preferably 450,000 or less, more preferably 400,000 or less, more preferably 350,000 or less, particularly preferably 330,000 or less, more particularly preferably 320,000 or less, and most preferably 300,000 or less. In addition, the hydrogenated block copolymers described in the first and second embodiments of the present invention show good flexibility, rubber elasticity and elongation characteristics even in a low temperature region, and therefore, are preferably used as resin modifiers for improving the impact resistance of other resins, etc. In the case of using the hydrogenated block copolymer as the resin modifier, from the viewpoint of easily obtaining more excellent impact resistance, the upper limit of the weight average molecular weight (Mw) of the hydrogenated block copolymer is preferably 250,000 or less, more preferably 200,000 or less, further preferably 180,000 or less, further preferably 150,000 or less, particularly preferably 130,000 or less, more particularly preferably 120,000 or less, and most preferably 110,000 or less.

[0156] The weight average molecular weight of the hydrogenated block copolymer can be adjusted to the above range by, for example, adjusting the amount of monomers relative to the polymerization initiator.

[0157] The hydrogenated block copolymer may have one or more functional groups such as carboxyl groups, hydroxyl groups, acid anhydride groups, amino groups, epoxy groups, etc. in the molecular chain and / or at the molecular ends, or may have no functional groups, unless the objects and effects of the present invention are impaired.

[0158] (Physical Properties of Hydrogenated Block Copolymer)

[0159] The hydrogenated product of the block copolymer may be a substance having a crystallization temperature of 0°C or less, or a substance having no crystallization temperature. When the crystallization temperature of the hydrogenated block copolymer is 0°C or less or when the crystallization temperature does not exist, the softness and rubber elasticity are improved. From the viewpoint of improving softness and rubber elasticity, when the hydrogenated block copolymer has a crystallization temperature, the crystallization temperature is more preferably -5°C or less, further preferably -10°C or less, further preferably -15°C or less, further preferably -20°C or less, further preferably -25°C or less, and particularly preferably -30°C or less. The lower limit of the crystallization temperature is not particularly limited, and is, for example, -70°C. In other words, the crystallization temperature of the hydrogenated block copolymer is preferably -70 to 0°C when it exists.

[0160] In addition, in this specification, the crystallization temperature of a hydrogenated block copolymer is measured by thermal analysis using DSC, and is specifically measured by the method described in Examples.

[0161] The crystallization temperature of the hydrogenated block copolymer can be set as described above by, for example, adjusting the polymerization conditions of the diene monomer.

[0162] The crystallization heat of the hydrogenated block copolymer may be 20 J / g or less, or there may be no crystallization temperature. When the crystallization heat of the hydrogenated block copolymer is 20 J / g or less or there is no crystallization temperature, the softness and rubber elasticity are improved. From the viewpoint of improving softness and rubber elasticity, the crystallization heat is more preferably 15 J / g or less, further preferably 10 J / g or less, further preferably 6 J / g or less, and particularly preferably there is no crystallization peak. The lower limit of the crystallization heat is not particularly limited, for example, 1 J / g. In other words, in the presence of a crystallization peak, the crystallization heat of the hydrogenated block copolymer is preferably 1 to 20 J / g.

[0163] In addition, in this specification, the heat of crystallization of the hydrogenated block copolymer is measured by thermal analysis using DSC, and specifically, it is measured by the method described in Examples.

[0164] The heat of crystallization of the hydrogenated block copolymer can be set as described above by, for example, adjusting the polymerization conditions of the diene monomer.

[0165] From the viewpoint of ensuring good elongation properties, the tensile elongation at break of the hydrogenated block copolymer measured in accordance with JIS K 6251 (2017) is preferably 300% or more, more preferably 400% or more, further preferably 500% or more, and further preferably 530% or more. The upper limit of the tensile elongation at break is not particularly limited, and from the viewpoint of ease of manufacture, it is, for example, 1,000%. In other words, the tensile elongation at break of the hydrogenated block copolymer is preferably 300 to 1,000%.

[0166] In addition, more specifically, the tensile elongation at break is measured according to the method described in Examples.

[0167] From the viewpoint of flexibility at low temperatures, the shear storage modulus G' at -40°C of the hydrogenated block copolymer measured by a complex shear viscosity test at a frequency of 1 Hz according to JIS K7244-10 (2005) is preferably 200 MPa or less, more preferably 100 MPa or less, further preferably 50 MPa or less, further preferably 25 MPa or less, particularly preferably 15 MPa or less, and most preferably 10 MPa or less. The lower limit of the shear storage modulus G' is not particularly limited, and from the viewpoint of mechanical strength, it is, for example, 0.1 MPa. In other words, the shear storage modulus G' at -40°C of the hydrogenated block copolymer is preferably 0.1 to 200 MPa.

[0168] It should be noted that, in more detail, the shear storage modulus G' is measured according to the method described in the Examples.

[0169] According to JIS K7244-10 (2005), the peak strength of the loss tangent tanδ of the hydrogenated block copolymer measured under the conditions of a strain of 1%, a frequency of 1 Hz, a measurement temperature of -80 to 0°C, a heating rate of 3°C / min, and a shear mode, the larger the value, the better the flexibility at low temperatures, and if it is 0.3 or more, sufficient flexibility at low temperatures can be obtained. The peak strength of tanδ is preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 0.6 or more.

[0170] In addition, from the viewpoint of ensuring sufficient flexibility and rubber elasticity in a low temperature range, the peak top temperature of the loss tangent tanδ of the hydrogenated block copolymer measured under the conditions of a strain of 1%, a frequency of 1 Hz, a measurement temperature of -80 to 0°C, a heating rate of 3°C / min, and a shear mode according to JIS K7244-10 (2005) is preferably -40°C or less, more preferably -45°C or less, and further preferably -50°C or less. The lower limit of the peak top temperature of the loss tangent tanδ is not particularly limited, but from the viewpoint of ease of production, it is, for example, -70°C. In other words, the peak top temperature of the loss tangent tanδ of the hydrogenated block copolymer is preferably -70 to -40°C.

[0171] It should be noted that the peak intensity of tan δ refers to the tan δ value when the peak of tan δ reaches the maximum. In addition, the peak temperature of tan δ refers to the temperature when the peak of tan δ reaches the maximum. Specifically, the peak temperature of tan δ and the peak intensity of tan δ of the hydrogenated block copolymer are measured by the method described in the examples.

[0172] In order to make these values ​​into the said range, for example, the ratio of isoprene which is a monomer for forming the polymer block (B) can be adjusted.

[0173] [Resin composition]

[0174] The first embodiment of the resin composition of the present invention is a resin composition, wherein, as component (a), it contains a hydrogenated product of the above-mentioned block copolymer, and as component (b), it contains one or more oil components selected from mineral oil, vegetable oil and ethylene / α-olefin copolymer oligomers, and the content ratio (a) / (b) of component (a) to component (b) is 1 / 99 to 99 / 1 in terms of mass ratio.

[0175] It should be noted that in one embodiment, the total content of component (a) and component (b) in the above composition is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, particularly preferably 90% by mass or more, and most preferably 95% by mass or more.

[0176] Examples of the mineral oil include paraffinic oil, cycloparaffinic oil, and aromatic oil, and examples of the vegetable oil include peanut oil and rosin.

[0177] The resin composition contains the hydrogenated block copolymer as the component (a) and the oil component as the component (b), thereby making it possible to obtain a resin composition having high strength and oil retention even in a low temperature range of around -20°C or lower.

[0178] From the viewpoint of achieving both mechanical properties and low-temperature properties of the resin composition, the content ratio (a) / (b) of component (a) to component (b) in the above-mentioned resin composition is preferably 1 / 99 to 80 / 20, more preferably 3 / 97 to 70 / 30, further preferably 4 / 96 to 60 / 40, and further preferably 5 / 95 to 55 / 45 in terms of mass ratio.

[0179] A second embodiment of the resin composition of the present invention is a resin composition, wherein as component (a), a hydrogenated product of the above-mentioned block copolymer is contained, and as component (c), at least one selected from polyethylene, polypropylene, styrene-based resins, polyphenylene ethers, polyester resins, polycarbonates, polyacetals, polyamides, polyarylene sulfides, polyarylates, polyimides, polyetheretherketones, and liquid crystal polyesters is contained, and the content ratio (a) / (c) of component (a) to component (c) is 1 / 99 to 99 / 1 in terms of mass ratio.

[0180] It should be noted that in one embodiment, the total content of component (a) and component (c) in the above-mentioned resin composition is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, further preferably 85% by mass or more, particularly preferably 90% by mass or more, and most preferably 95% by mass or more.

[0181] By containing the hydrogenated block copolymer as the component (a) in the resin composition, the impact resistance and thermal shock resistance can be improved in a low temperature range of around -20°C or lower than -20°C, compared with the component (c), which is the resin component before the addition of the component (a).

[0182] From the viewpoint of achieving both mechanical properties and low-temperature properties of the resin composition, the content ratio (a) / (c) of component (a) to component (c) in the above-mentioned resin composition is preferably 1 / 99 to 50 / 50, more preferably 3 / 97 to 30 / 70, further preferably 4 / 96 to 25 / 75, and further preferably 5 / 95 to 20 / 80 in terms of mass ratio.

[0183] When the resin composition comprising the above-mentioned components (a) and (c) is used for applications where impact resistance is important, it is more preferable to further contain an ethylene-α-olefin copolymer rubber (d).

[0184] <Ethylene-α-olefin copolymer rubber (d)>

[0185] The ethylene-α-olefin copolymer rubber (d) is a copolymer of ethylene and α-olefin.

[0186] (α-Olefins)

[0187] The α-olefin constituting the ethylene-α-olefin copolymer rubber (d) is not particularly limited, and examples thereof include α-olefins having 3 to 20 carbon atoms (hereinafter referred to as "C3 to C20"). The C3 to C20 α-olefins may be either linear or branched, and examples thereof include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, 4-methyl-1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 3,3-dimethyl-1-butene, diethyl-1-butene, trimethyl-1-butene, 3-methyl-1-butene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, 4-methyl-1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 3,3-dimethyl-1-butene, 1-ethyl ... Pentene, ethyl-1-pentene, propyl-1-pentene, dimethyl-1-pentene, methylethyl-1-pentene, diethyl-1-hexene, trimethyl-1-pentene, 3-methyl-1-hexene, dimethyl-1-hexene, 3,5,5-trimethyl-1-hexene, methylethyl-1-heptene, trimethyl-1-heptene, dimethyloctene, ethyl-1-octene, methyl-1-nonene, vinylcyclopentene, vinylcyclohexene, vinylnorbornene, etc. These can be used alone or in combination. Among these, from the viewpoint of impact resistance and tensile elongation at break, preferably C4 to C8 α-olefin comonomers, more preferably at least one selected from propylene, 1-butene, 1-hexene, 4-methyl-1-pentene and 1-octene, from the viewpoint of impact resistance, more preferably at least one selected from propylene, 1-butene and 1-octene, particularly preferably 1-octene. On the other hand, from the viewpoint of moldability, at least one selected from propylene, 1-butene and 1-octene is further preferred, and propylene is particularly preferred. In the case where the α-olefin constituting the ethylene-α-olefin copolymer rubber (d) is propylene and the component (c) is polypropylene, it is also preferred to use multi-stage polymerization to prepare the polypropylene as the component (c). In more detail, one of the preferred embodiments of the present invention is that the isotactic polypropylene resin is polymerized in the front stage of the polymerization, and the ethylene-propylene copolymer is polymerized in the back stage, and then they are mixed.

[0188] The content of α-olefin in the ethylene-α-olefin copolymer rubber (d) is not particularly limited, but is preferably 5 to 50% by mass, more preferably 20 to 45% by mass. If the content of α-olefin in the ethylene-α-olefin copolymer rubber (d) is above the aforementioned lower limit, there is a tendency for low-temperature curing resistance and flexibility to become good, and if it is below the aforementioned upper limit, there is a tendency for rigidity to become good.

[0189] As the ethylene-α-olefin copolymer rubber (d), two or more ethylene-α-olefin copolymer rubbers can be used. In this case, from the viewpoint of further improving impact resistance, tensile elongation at break and rigidity, for example, two or more ethylene-α-olefin copolymer rubbers having different densities can be used in combination.

[0190] The melt flow rate (MFR) of the ethylene-α-olefin copolymer rubber (d) is not particularly limited, but is preferably 0.1 to 50 g / 10 minutes, more preferably 0.3 to 35 g / 10 minutes. If the melt flow rate (MFR) of the ethylene-α-olefin copolymer rubber (d) is above the lower limit, processability tends to be improved, and if it is below the upper limit, mechanical properties tend to be improved.

[0191] The molecular weight distribution (Mw / Mn; Mw is a weight average molecular weight, and Mn is a number average molecular weight) of the ethylene-α-olefin copolymer rubber (d) is not particularly limited, but is preferably 1.3 to 5.0.

[0192] The density of the ethylene-α-olefin copolymer rubber (d) is not particularly limited, but is preferably 0.850 to 0.910 g / cm 3 , more preferably 0.855 to 0.885 g / cm 3 When the density of the ethylene-α-olefin copolymer rubber (d) is at least the above lower limit, the rigidity tends to be good, and when it is at most the above upper limit, the impact resistance and the tensile elongation at break tend to be good.

[0193] The catalyst for preparing the ethylene-α-olefin copolymer rubber (d) is not particularly limited, and examples thereof include catalysts that can easily obtain a high molecular weight α-olefin copolymer under processing conditions (e.g., catalysts based on titanium, metallocene or vanadium). These catalysts may be used alone or in combination of two or more. Among these, metallocene catalysts and titanium chloride are preferred from the viewpoint of structural control stability.

[0194] The polymerization form of the ethylene-α-olefin copolymer rubber (d) is not particularly limited, and random copolymers of ethylene and α-olefins, block copolymers of ethylene and α-olefins, etc. can be used. As specific examples, "TAFMER (registered trademark)" manufactured by Mitsui Chemicals, Inc. as a random copolymer rubber of ethylene and 1-butene, "ENGAGE (registered trademark)" manufactured by DOW Co., Ltd. as a random copolymer rubber of ethylene and 1-octene, "INFUSE (registered trademark)" manufactured by DOW Co., Ltd. as a block copolymer rubber of ethylene and 1-octene, etc. can be cited, but are not limited to them.

[0195] The content of the ethylene-α-olefin copolymer rubber (d) in the resin composition is not particularly limited, but is preferably 1 to 50 parts by weight, more preferably 5 to 40 parts by weight, further preferably 8 to 30 parts by weight, and particularly preferably 10 to 20 parts by weight relative to 100 parts by weight of the component (c). If the content of the ethylene-α-olefin copolymer rubber (d) is above the lower limit, the impact resistance and tensile elongation at break tend to be good, and if it is below the upper limit, the rigidity tends to be good.

[0196] In addition, when the above-mentioned resin composition includes components (a), (c) and (d), from the viewpoint of the balance between rigidity and impact resistance, the resin composition more preferably includes polyethylene as component (c). As the polyethylene, there is no particular limitation, and polyethylenes such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE) can be listed. They can be used alone or in combination of two or more. Among these, from the viewpoint of maintaining the impact resistance of the above-mentioned resin composition and obtaining higher rigidity, polyethylenes such as medium-density polyethylene (MDPE) and high-density polyethylene (HDPE) are preferably used, and high-density polyethylene (HDPE) is particularly preferably used.

[0197] When the resin composition contains polyethylene, the content of the polyethylene in the resin component of the resin composition is not particularly limited, but is preferably 30% by mass or less, more preferably 25% by mass or less, further preferably 22% by mass or less, particularly preferably 20% by mass or less, and is preferably 1% by mass or more, more preferably 3% by mass or more, further preferably 5% by mass or more, and particularly preferably 7% by mass or more, from the viewpoint of impact resistance, tensile elongation at break and rigidity.

[0198] The resin composition may contain, as resin components other than the components (a) to (d) above, hydrogenated resins such as hydrogenated coumarone-indene resins, hydrogenated rosin resins, hydrogenated terpene resins, and alicyclic hydrogenated petroleum resins; tackifying resins such as aliphatic resins formed from olefin and diene polymers; and other polymers such as hydrogenated polyisoprene, hydrogenated polybutadiene, butyl rubber, polyisobutylene, and polybutene, within the range not impairing the effects of the present invention.

[0199] When the resin composition contains resin components other than components (a) to (d), there is no particular limitation, but the content of components other than components (a) to (d) in the composition is preferably 50% by mass or less. In this case, from the viewpoint of impact resistance and rubber elasticity at low temperatures, the content of the hydrogenated block copolymer according to an embodiment of the present invention in the composition is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, particularly preferably 90% by mass or more, and most preferably 95% by mass or more.

[0200] <Additives>

[0201] As the components other than the resin component that can be included in the above-mentioned resin combination, for example antioxidants, ultraviolet light absorbers, light stabilizers, heat insulating materials, anti-blocking agents, pigments, dyes, softeners, crosslinking agents, crosslinking aids, crosslinking accelerators, fillers, reinforcing materials, lubricants, antistatic agents, flame retardants, foaming agents, water repellents, waterproofing agents, electrical conductivity imparting agents, thermal conductivity imparting agents, electromagnetic wave shielding imparting agents, fluorescent agents, antibacterial agents and other additives can be listed, but are not particularly limited to them. They can be used alone or in combination of two or more.

[0202] Examples of the antioxidant include phenolic antioxidants, phosphorus antioxidants, and sulfur antioxidants.

[0203] As the ultraviolet absorber, in addition to benzotriazole-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, benzoate-based ultraviolet absorbers, etc., triazine-based compounds, benzophenone-based compounds, malonic acid ester compounds, anilide oxalate compounds, etc. can also be used.

[0204] As a light stabilizer, a hindered amine light stabilizer etc. are mentioned, for example.

[0205] As heat-insulating materials, materials obtained by, for example, making glass contain heat-shielding particles with heat-shielding function, and organic pigment compounds with heat-shielding function, etc. As particles with heat-shielding function, particles of oxides such as tin-doped indium oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, tin-doped zinc oxide, and silicon-doped zinc oxide, particles of inorganic materials with heat-shielding function such as LaB6 (lanthanum hexaboride) particles, etc., can be listed. In addition, as organic pigment compounds with heat-shielding function, diimmonium-based pigments, aluminum-based pigments, phthalocyanine-based pigments, anthraquinone-based pigments, polymethine-based pigments, benzenedithiol-type ammonium-based compounds, thiourea derivatives, and thiol-metal complexes can be listed.

[0206] As anti-blocking agents, inorganic particles and organic particles can be listed. As inorganic particles, oxides, hydroxides, sulfides, nitrides, halides, carbonates, sulfates, acetates, phosphates, phosphites, organic carboxylates, silicates, titanates, borates and their hydrated compounds, as well as composite compounds with these as the core and natural mineral particles can be listed.

[0207] Examples of the pigment include organic pigments and inorganic pigments. Examples of the organic pigment include azo pigments, quinacridone pigments, and phthalocyanine pigments. Examples of the inorganic pigment include titanium oxide, zinc oxide, zinc sulfide, carbon black, lead pigments, cadmium pigments, cobalt pigments, iron pigments, chromium pigments, ultramarine, and Prussian blue.

[0208] Examples of the dye include azo, anthraquinone, phthalocyanine, quinacridone, perylene, dioxazine, anthraquinone, indolinone, isoindolinone, quinoneimine, triphenylmethane, thiazole, nitro, and nitroso dyes.

[0209] Known softeners such as phosphate esters, low molecular weight polyethylene glycol, hydrocarbon synthetic oils such as liquid polybutene, liquid polyisoprene or its hydrogenate, liquid polybutadiene or its hydrogenate, etc. can be used. These can be used alone or in combination of two or more.

[0210] Examples of the cross-linking agent include radical generators, sulfur, and sulfur compounds.

[0211] Examples of the free radical generator include dialkyl monoperoxides such as diisopropylbenzene peroxide, di-tert-butyl peroxide, and tert-butyl isopropylbenzene peroxide; diperoxides such as 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, bis(tert-butyldioxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and n-butyl 4,4-bis(tert-butylperoxy)valerate; peroxides containing a benzoyl group such as benzoyl peroxide, p-chlorobenzoyl peroxide, and 2,4-dichlorobenzoyl peroxide; monoacyl alkyl peroxides such as tert-butyl peroxybenzoate; percarbonic acids such as tert-butyl peroxyisopropyl carbonate; and diacyl peroxides such as diacetyl peroxide and lauroyl peroxide. These may be used alone or in combination of two or more. Among them, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and diisopropylbenzene peroxide are preferred from the viewpoint of reactivity.

[0212] Examples of the sulfur compound include sulfur monochloride and sulfur dichloride.

[0213] As the crosslinking agent, in addition to these, a combination of p-quinone dioxime and lead dioxide, a combination of p,p'-dibenzoylquinone dioxime and trilead tetroxide, or the like may be used.

[0214] As the crosslinking aid, a known crosslinking aid can be used, for example, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, triallyl trimellitate, triallyl 1,2,4-benzenetricarboxylate, triallyl isocyanurate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, polyethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, divinylbenzene, glycerol dimethacrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate and other multifunctional monomers; stannous chloride, ferric chloride, organic sulfonic acid, polychloroprene, chlorosulfonated polyethylene, etc. The crosslinking aid can be used alone or in combination of two or more.

[0215] Examples of the crosslinking accelerator include thiazoles such as N,N-diisopropyl-2-benzothiazole-sulfenamide, 2-mercaptobenzothiazole, and 2-(4-morpholinodithio)benzothiazole; guanidines such as diphenylguanidine and triphenylguanidine; aldehyde-amine reactants or aldehyde-ammonia reactants such as butyraldehyde-aniline reactants and hexamethylenetetramine-acetaldehyde reactants; imidazolines such as 2-mercaptoimidazoline; thiocarbanilide, diethylurea, dibutylthiourea, trimethylthiourea, di-o-toluene. Thioureas such as thiourea; dibenzothiazolyl disulfide; thiuram monosulfides or thiuram polysulfides such as tetramethylthiuram monosulfide, tetramethylthiuram disulfide, and pentamethylenethiuram tetrasulfide; thiocarbamates such as zinc dimethyldithiocarbamate, zinc ethylphenyldithiocarbamate, sodium dimethyldithiocarbamate, selenium dimethyldithiocarbamate, and tellurium diethyldithiocarbamate; xanthates such as zinc dibutyl xanthate; zinc white, etc. The crosslinking accelerator may be used alone or in combination of two or more.

[0216] As fillers, for example, talc, clay, mica, calcium silicate, glass, glass hollow spheres, glass fibers, calcium carbonate, magnesium carbonate, basic magnesium carbonate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, zinc borate, dawsonite, ammonium polyphosphate, calcium aluminate, hydrotalcite, silica, diatomaceous earth, aluminum oxide, titanium oxide, iron oxide, zinc oxide, magnesium oxide, tin oxide, antimony oxide, barium ferrite, strontium ferrite, carbon fiber, activated carbon, carbon hollow spheres, calcium titanate, lead zirconate titanate, silicon carbide and other inorganic fillers; wood powder, starch and other organic fillers; carbon black, graphite, carbon nanotubes and other conductive fillers; silver powder, copper powder, nickel powder, tin powder, copper fiber, stainless steel fiber, aluminum fiber, iron fiber and other metal fillers, etc. Among these, from the viewpoint of the balance between rigidity and impact resistance, talc, calcium carbonate, glass fiber and carbon fiber are preferred, and talc and glass fiber are more preferred. When a filler is contained, its content is not particularly limited, and is preferably 5 to 30 parts by mass, more preferably 10 to 25 parts by mass, and particularly preferably 15 to 23 parts by mass relative to 100 parts by mass of the total resin components in the resin composition. If the content of the filler is above the lower limit, there is a tendency for rigidity and impact resistance to become good, and if it is below the upper limit, there is a tendency for impact resistance and tensile elongation at break to become good.

[0217] The content of the additive contained in the resin composition is not particularly limited and can be appropriately adjusted according to the type of the additive. When the resin composition contains the additive, the content of the additive can be, for example, 50% by mass or less, 45% by mass or less, or 30% by mass or less relative to the total mass of the resin composition. In addition, it can be 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more. In other words, the content of the additive is preferably 0.01 to 50% by mass relative to the total mass of the resin composition.

[0218] <Physical Properties of Resin Composition>

[0219] (Tensile Strength)

[0220] The tensile strength of the above-mentioned resin composition can be set to, for example, 0.10MPa or more, or 0.20MPa or more, 0.30MPa or more, or 0.40MPa or more. The upper limit of the tensile strength is not particularly limited, and is usually 50.0MPa or less, and can be 1.0MPa or less. In other words, the tensile strength of the resin composition is, for example, 0.10 to 50.0MPa. By making the tensile strength of the resin composition within the above range, a resin composition with good mechanical properties can be obtained.

[0221] In addition, the tensile strength in this specification refers to the value measured by the method based on JIS K 6251 (2017), and specifically refers to the value measured by the measurement method described in the Examples.

[0222] (Tensile properties)

[0223] As the tensile property of the resin composition, the tensile modulus can be, for example, 100 MPa or more, 350 MPa or more, 500 MPa or more, or 700 MPa or more. The upper limit of the tensile modulus is not particularly limited, but is usually 2,000 MPa or less, and can be 1,000 MPa or less.

[0224] As the tensile property of the resin composition, the yield stress can be set to 5 MPa or more, 10 MPa or more, 15 MPa or more, or 20 MPa or more. The upper limit of the yield stress is not particularly limited, but is usually 60 MPa or less, and can be 50 MPa or less.

[0225] As the tensile property of the resin composition, the tensile elongation at break at 23° C. can be, for example, 100% or more, 200% or more, 300% or more, or 400% or more. The upper limit of the tensile elongation at break at 23° C. is not particularly limited, but is generally 1,000% or less, and can be 600% or less.

[0226] The tensile elongation at break at -20°C may be, for example, 30% or more, 50% or more, 70% or more, or 100% or more. The upper limit of the tensile elongation at break at -20°C is not particularly limited, but is usually 350% or less, and may be 300% or less.

[0227] By setting the tensile properties of the resin composition to be within the above range, a resin composition having good mechanical properties can be obtained.

[0228] In addition, the tensile property in this specification refers to the value measured by the method based on JIS K 7161 (2014), and specifically refers to the value measured by the measurement method described in the Example.

[0229] The higher the oil retention rate of the resin composition, the more preferred it is, for example, 50% or more, preferably 60% or more, and more preferably 70% or more at both room temperature and low temperature. The upper limit of the oil retention rate is not particularly limited, but is usually 95% or less, and can be 90% or less. By making the oil retention rate of the resin composition within the above range, high stability can be exhibited during long-term storage.

[0230] It should be noted that the oil retention rate in this specification refers to a value calculated by leaving a resin composition of a predetermined size at a predetermined temperature for a predetermined time and measuring the change in weight thereof, and specifically refers to a value measured by the measurement method described in the Examples.

[0231] The Charpy impact strength of the resin composition can be set to 5 kJ / m 2 Above, it can also be set to 10kJ / m 2 Above, 15kJ / m 2 Above, further, it can also be set to 20kJ / m 2 The upper limit of Charpy impact strength is not particularly limited, but is usually 80 kJ / m 2 Below, can be 70kJ / m 2 When the Charpy impact strength of the resin composition is within the above range, the resin composition is less likely to be broken by impact.

[0232] It should be noted that the Charpy impact strength in this specification refers to a value measured by an impact strength tester for a test piece prepared in accordance with JIS K7111-1 (2012), and specifically refers to a value measured by the measurement method described in the Examples.

[0233] The flexural strength of the resin composition may be, for example, 10 MPa or more, 15 MPa or more, 18 MPa or more, or 20 MPa or more. The upper limit of the flexural strength is not particularly limited, but is usually 50 MPa or less, and may be 40 MPa or less.

[0234] The flexural modulus of the resin composition may be, for example, 500 MPa or more, 700 MPa or more, 800 MPa or more, or 900 MPa or more. The upper limit of the flexural modulus is not particularly limited, but is usually 1,500 MPa or less, and may be 1,200 MPa or less.

[0235] By setting the flexural strength and flexural modulus of the resin composition to be within the above ranges, a resin composition having good mechanical properties can be obtained.

[0236] In addition, the flexural strength and flexural modulus in this specification refer to values ​​measured in accordance with JIS K 7171 (ISO 178), and specifically, refer to values ​​measured by the measurement method described in the Examples.

[0237] The melt flow rate value (MFR) at 23 ° C and 2.16 kg load measured according to JIS K7210:2014 of the above-mentioned resin composition can be set to, for example, 2.5 g / 10 min or more, 3.0 g / 10 min or more, 3.5 g / 10 min or more, and further, 4.0 g / 10 min or more. The upper limit of MFR is not particularly limited, usually 20 g / 10 min or less, and can be 10 g / 10 min or less. By making the MFR of the resin composition within the above range, good fluidity can be ensured.

[0238] In addition, MFR in this specification means the value measured according to JIS K 7210:2014, and specifically means the value measured by the measurement method described in the Examples.

[0239] [Gel composition]

[0240] The gel composition according to the embodiment of the present invention contains, as component (α), the hydrogenated block copolymer of the present embodiment and a base oil (β). The base oil (β), other components, the composition of the gel composition, the physical properties of the gel composition, etc. are described below.

[0241] <Base oil (β)>

[0242] Examples of the base oil (β) used in the gel composition according to the present embodiment include mineral oil, synthetic oil, and vegetable oil.

[0243] Examples of mineral oils include paraffinic mineral oils obtained by common refining methods such as solvent refining and hydrorefining; cycloparaffinic mineral oils; waxes produced by the Fischer-Tropsch process (GTL wax); and mineral oils produced by isomerizing waxes.

[0244] Examples of synthetic oils include hydrocarbon synthetic oils and ether synthetic oils. Examples of hydrocarbon synthetic oils include α-olefin oligomers such as polybutene, polyisobutylene, 1-octene oligomers, 1-decene oligomers, and ethylene-propylene copolymers, or hydrogenated products thereof; alkylbenzenes; and alkylnaphthalenes. Examples of ether synthetic oils include polyoxyalkylene glycols and polyphenyl ethers.

[0245] Examples of the vegetable oil include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, and peanut oil.

[0246] Mineral oils, synthetic oils, and vegetable oils used as the base oil (β) are classified into Groups I, II, III, IV, and V in the base oil classification of the American Petroleum Institute (API).

[0247] The base oil (β) may be one selected from mineral oil, synthetic oil and vegetable oil, or may be two or more mineral oils, two or more synthetic oils, two or more vegetable oils, or a mixture of one or more of each of mineral oil, synthetic oil and vegetable oil.

[0248] When the gel composition is used as part or all of the cable filling material described below, from the viewpoint of obtaining a gel composition having a viscosity suitable for a cable filling material even when the blending ratio of the hydrogenated block copolymer as the component (α) in the gel composition is small, a mineral oil is preferred, and at least one selected from a paraffinic mineral oil and a cycloparaffinic mineral oil is more preferred. Furthermore, from the viewpoint of increasing the dropping point of the gel composition by making the polymer block (A) in the hydrogenated block copolymer difficult to plasticize, a paraffinic mineral oil is further preferred. Furthermore, paraffinic mineral oils classified into Group II and Group III are preferred because they have a small sulfur component and a large saturated component, and mineral oils classified into Group II are particularly preferred.

[0249] When the gel composition is used as part or all of a cosmetic, as the base oil (β), one selected from mineral oil, synthetic oil and vegetable oil may be used; two or more mineral oils, two or more synthetic oils and two or more vegetable oils may be used; or a mixture of one or more of each of mineral oil, synthetic oil and vegetable oil may be used. From the viewpoint of purity, mineral oils or synthetic oils of Groups III, IV and V are preferred.

[0250] In addition, poly-α-olefins (abbreviation: PAO) classified into the aforementioned Group IV may also be used.

[0251] When the gel composition is used as part or all of a lubricating oil, as the base oil (β), one selected from mineral oil, synthetic oil and vegetable oil may be used; two or more mineral oils, two or more synthetic oils and two or more vegetable oils may be used; or a mixture of one or more of each of mineral oil, synthetic oil and vegetable oil may be used. From the viewpoint of economic efficiency, mineral oil is preferred.

[0252] When the gel composition is used as part or all of a grease, as the base oil (β), one selected from a mineral oil, a synthetic oil and a vegetable oil may be used; two or more mineral oils, two or more synthetic oils and two or more vegetable oils, or a mixture of one or more of each of mineral oils, synthetic oils and vegetable oils may be used; base oils classified into Group I, Group II and Group III are preferred because the raw materials are easily available; base oils classified into Group II and Group III are more preferred because they have a small sulfur component and a large saturated component; base oils classified into the aforementioned Group II and Group III are more preferably mineral oils classified into Group II and Group III, and mineral oils classified into Group II are still more preferred.

[0253] In addition, poly-α-olefins (abbreviation: PAO) classified into the aforementioned Group IV may also be used.

[0254] The 40° C. kinematic viscosity of the base oil (β) can be appropriately selected depending on the application of the grease composition to be obtained, and is preferably 5 to 1,000 mm 2 / s, more preferably 10 to 500 mm 2 / s, more preferably 20 to 200 mm 2 / s, particularly preferably 25 to 50 mm 2 / s.

[0255] When the gel composition is used as part or all of a grease, the content of the base oil (β) is preferably 70 to 99 mass %, more preferably 75 to 99 mass %, further preferably 80 to 99 mass %, particularly preferably 85 to 99 mass %, based on 100 mass % of the total amount of the gel composition.

[0256] The base oil (β) preferably contains paraffins or a combination of paraffins and cycloparaffins, and the mass ratio of paraffins to cycloparaffins [paraffins / cycloparaffins] is preferably 10 / 90 to 100 / 0. When the mass ratio of paraffins to cycloparaffins is within the above range, the polymer block (A) in the hydrogenated block copolymer is less likely to be plasticized.

[0257] When the gel composition according to the present embodiment is used as a part or all of a cable filling material, the mass ratio of paraffin to cycloparaffin [paraffin / cycloparaffin] is preferably 10 / 90 to 90 / 10, more preferably 20 / 80 to 90 / 10, further preferably 30 / 70 to 90 / 10, further preferably 40 / 60 to 90 / 10, further preferably 50 / 50 to 90 / 10, further preferably 60 / 40 to 90 / 10, and particularly preferably 60 / 40 to 80 / 20 from the viewpoint of improving the dropping point of the gel composition.

[0258] When the gel composition according to the present embodiment is used as part or all of a cosmetic or lubricating oil, the base oil (β) preferably contains paraffin or a combination of paraffin and cycloparaffin, and the mass ratio of paraffin to cycloparaffin [paraffin / cycloparaffin] is preferably 10 / 90 to 100 / 0, more preferably 20 / 80 to 100 / 0, further preferably 30 / 70 to 100 / 0, further preferably 40 / 60 to 100 / 0, further preferably 50 / 50 to 100 / 0, further preferably 60 / 40 to 100 / 0, and particularly preferably 70 / 30 to 100 / 0.

[0259] When the gel composition according to the present embodiment is used as part or all of a grease, the mass ratio of paraffin to cycloparaffin [paraffin / cycloparaffin] is preferably 10 / 90 to 100 / 0, more preferably 20 / 80 to 100 / 0, further preferably 30 / 70 to 100 / 0, further preferably 40 / 60 to 100 / 0, further preferably 50 / 50 to 100 / 0, further preferably 60 / 40 to 100 / 0, further preferably 70 / 30 to 100 / 0, and particularly preferably 70 / 30 to 90 / 10, from the viewpoint of the availability of the base oil (β), the economy, and the oxidation stability of the grease.

[0260] The viscosity index of the base oil (β) is preferably 70 or more, more preferably 80 or more, further preferably 90 or more, particularly preferably 100 or more, and is preferably 150 or less, more preferably 145 or less, further preferably 140 or less, further preferably 135 or less, particularly preferably 120 or less.

[0261] <Other ingredients>

[0262] The gel composition described in this embodiment may contain other components such as antioxidants, surfactants, pour point depressants, defoamers, gelling agents, viscosity index improvers, thickeners, water absorbents, flame retardants, fillers, tackifying resins, thixotropic agents, petroleum waxes, metal passivators, copper inert agents, friction modifiers, rust inhibitors, detergents and dispersants, extreme pressure agents, thickeners, etc. as needed. These additives may be used alone or in combination of two or more.

[0263] It should be noted that when the gel composition as the grease contains a thickener, the content of the thickener in the gel composition can be appropriately adjusted so that the working cone penetration, mixing stability, oil separation and water resistance of the grease are within the desired range, and is preferably 1 to 40 mass%, more preferably 2 to 30 mass%, further preferably 3 to 20 mass%, further preferably 4 to 18 mass%, further preferably 5 to 16 mass%, and particularly preferably 6 to 12 mass%. If the content of the thickener in the gel composition is within the above range, there is a tendency that the balance between the performance and economic efficiency of the grease is excellent.

[0264] <Content of Hydrogenated Block Copolymer>

[0265] The content of the hydrogenated block copolymer as the component (α) in the gel composition according to the present embodiment is preferably 0.10 to 30.00 parts by mass, more preferably 0.25 to 27.00 parts by mass, further preferably 0.50 to 25.00 parts by mass, further preferably 0.75 to 23.00 parts by mass, further preferably 0.75 to 20.00 parts by mass, and particularly preferably 0.75 to 18.00 parts by mass, based on 100 parts by mass of the total of the hydrogenated block copolymer and the base oil (β).

[0266] When the gel composition according to the present embodiment is used as a cable filling material, the content of the hydrogenated block copolymer as the component (α) in the gel composition is preferably 1 to 20 parts by mass, more preferably 2 to 18 parts by mass, further preferably 4 to 16 parts by mass, further preferably 6 to 14 parts by mass, and particularly preferably 7 to 13 parts by mass, relative to 100 parts by mass of the total of the hydrogenated block copolymer and the base oil (β). When the content of the hydrogenated block copolymer (a) in the gel composition is within the above range, the gel composition as a cable filling material can be easily filled into a protective tube or a cable when manufacturing the cable.

[0267] When the gel composition according to the present embodiment is used as a cosmetic, the content of the hydrogenated block copolymer as the component (α) in the gel composition is preferably in the same range as when it is used as a cable filler. When the content of the hydrogenated block copolymer in the gel composition is within the above range, it is easy to fill the cosmetic composition into a container or use it when manufacturing the cosmetic.

[0268] When the gel composition according to the present embodiment is used as a lubricating oil, the suitable content of the hydrogenated block copolymer as the component (α) in the gel composition is preferably 0.1 to 10.0 parts by mass, more preferably 0.2 to 5.0 parts by mass, further preferably 0.3 to 4.0 parts by mass, further preferably 0.4 to 3.0 parts by mass, and particularly preferably 0.5 to 2.0 parts by mass, relative to 100 parts by mass of the total of the hydrogenated block copolymer and the base oil (β). When the content of the hydrogenated block copolymer in the gel composition is within the above range, there is a tendency that the balance between the performance and economic efficiency of the lubricating oil is excellent.

[0269] When the gel composition according to the present embodiment is used as a grease, the suitable content of the hydrogenated block copolymer as the component (α) in the gel composition is preferably 0.1 to 10.0 parts by mass, more preferably 0.2 to 5.0 parts by mass, further preferably 0.2 to 4.5 parts by mass, further preferably 0.3 to 4.0 parts by mass, further preferably 0.5 to 4.0 parts by mass, further preferably 1.0 to 4.0 parts by mass, further preferably 1.5 to 4.0 parts by mass, and particularly preferably 1.8 to 3.5 parts by mass, relative to 100 parts by mass of the total of the hydrogenated block copolymer and the base oil (β). When the content of the hydrogenated block copolymer in the gel composition is within the above range, there is a tendency that the balance between the performance and economic efficiency of the grease is excellent.

[0270] <Base oil (β) content>

[0271] The content of the base oil (β) in the gel composition is preferably 70.00 parts by mass or more, more preferably 73.00 parts by mass or more, further preferably 75.00 parts by mass or more, particularly preferably 77.00 parts by mass or more, based on 100 parts by mass of the total of the hydrogenated block copolymer as the component (α) and the base oil (β). The upper limit thereof is preferably 99.90 parts by mass, more preferably 99.75 parts by mass, further preferably 99.50 parts by mass, particularly preferably 99.25 parts by mass.

[0272] When the gel composition according to the present embodiment is used as a cable filling material, the content of the base oil (β) in the gel composition is preferably 80 parts by mass or more, more preferably 83 parts by mass or more, and particularly preferably 86 parts by mass or more, relative to 100 parts by mass of the total of the hydrogenated block copolymer as the component (α) and the base oil (β), and the upper limit thereof is preferably 99 parts by mass or less, more preferably 97 parts by mass or less, and particularly preferably 94 parts by mass or less. When the content of the base oil (β) in the gel composition is within the above range, when the gel composition is used as a cable filling material during the manufacture of the cable, the gel composition can be easily filled into a protective tube or a cable.

[0273] When the gel composition according to the present embodiment is used as a cosmetic, the content of the base oil (β) in the gel composition is preferably 80 parts by mass or more, more preferably 83 parts by mass or more, and particularly preferably 86 parts by mass or more, relative to 100 parts by mass of the total of the hydrogenated block copolymer as the component (α) and the base oil (β), and the upper limit is preferably 99 parts by mass or less, more preferably 97 parts by mass or less, and particularly preferably 94 parts by mass or less. When the content of the base oil (β) in the gel composition is within the above range, the cosmetic composition can be easily filled into a container or used when the cosmetic is produced.

[0274] When the gel composition according to the present embodiment is used as a lubricating oil, the content of the base oil (β) in the gel composition is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, and particularly preferably 96 parts by mass or more, relative to 100 parts by mass of the total of the hydrogenated block copolymer as the component (α) and the base oil (β), and the upper limit thereof is preferably 99.9 parts by mass or less, more preferably 99.8 parts by mass or less, and particularly preferably 99.7 parts by mass or less. When the content of the base oil (β) in the gel composition is within the above range, there is a tendency that the balance between the performance and economic efficiency of the lubricating oil is excellent.

[0275] When the gel composition according to the present embodiment is used as a grease, the content of the base oil (β) in the gel composition is preferably 90.0 parts by mass or more, more preferably 95.0 parts by mass or more, and particularly preferably 96.0 parts by mass or more, relative to 100 parts by mass of the total of the hydrogenated block copolymer (a) and the base oil (β), and the upper limit is preferably 99.9 parts by mass or less, more preferably 99.8 parts by mass or less, and particularly preferably 99.7 parts by mass or less. When the content of the base oil (β) in the gel composition is within the above range, there is a tendency that the balance between the performance and economic efficiency of the grease is excellent.

[0276] <Characteristics of Gel Composition>

[0277] (Drop point)

[0278] By using the hydrogenated block copolymer of the present embodiment, the dropping point of the gel composition (the temperature at which the gel composition changes from a semi-solid to a liquid) can be set to, for example, 195°C or more, or 197°C or more, 200°C or more, or 205°C or more. The upper limit of the dropping point is not particularly limited, but is generally 400°C or less, and may be 300°C or less. By setting the dropping point of the gel composition within the above range, when used as a cable filling material, the gel composition as a filling material is likely to exhibit the property that it does not flow out of the protective tube or the cable at a wide range of temperatures even when the protective tube is damaged, and in addition to the cable filling material, it is also likely to be used as a gel composition with excellent shape retention in a wide range of uses.

[0279] In addition, the dropping point in this specification means the value measured by the method based on JIS K 2220:2013.

[0280] (Cone Penetration)

[0281] By setting the cone penetration of the gel composition containing the hydrogenated block copolymer of the present embodiment to 360 to 430, when the gel composition according to the embodiment of the present invention is used as a cable filling material, it is possible to obtain a gel composition that is easy to protect the inside and has appropriate hardness. From the above viewpoint, the cone penetration of the gel composition is preferably 370 to 420, more preferably 375 to 390.

[0282] In addition, the cone penetration in this specification means the value measured by the method based on JIS K 2220:2013.

[0283] (Viscosity)

[0284] When the gel composition according to the embodiment of the present invention is used as a cable filling material, the gel composition can be used for 50 s to prevent the gel composition as a filling material from flowing out from the inside when the protective tube or cable is damaged. -1 The viscosity under the shear rate condition is preferably 500 mPa·s or more, more preferably 1,000 mPa·s or more, further preferably 2,000 mPa·s or more, further preferably 3,000 mPa·s or more, further preferably 3,500 mPa·s or more, and particularly preferably 4,000 mPa·s or more. From the viewpoint of easily filling the gel composition into a protective tube or a cable during cable production, the viscosity is preferably 300,000 mPa·s or less, more preferably 50,000 mPa·s or less, further preferably 30,000 mPa·s or less, and particularly preferably 20,000 mPa·s or less.

[0285] It should be noted that the viscosity in this specification refers to a value measured using a rheometer.

[0286] When the gel composition according to the present embodiment is used as a cosmetic, from the viewpoint of filling the cosmetic composition into a container or using the cosmetic composition during the production of the cosmetic, the gel composition is preferably -1 The viscosity under shear rate conditions is preferably from 500 mPa·s to 100,000 mPa·s, more preferably from 1,000 mPa·s to 50,000 mPa·s, further preferably from 2,000 mPa·s to 40,000 mPa·s, further preferably from 4,000 mPa·s to 30,000 mPa·s, further preferably from 9,000 mPa·s to 30,000 mPa·s, and particularly preferably from 15,000 mPa·s to 25,000 mPa·s.

[0287] (Kinematic viscosity)

[0288] When the gel composition according to this embodiment is used as a lubricating oil, the kinematic viscosity at 40° C. is preferably 40 to 300 mm 2 / sec, more preferably 50 to 150 mm 2 In addition, the kinematic viscosity at 100°C is preferably 3 to 30 mm 2 / sec, more preferably 4 to 20 mm 2 When the kinematic viscosity is within the above range, fuel efficiency can be reduced. The above kinematic viscosity is a value measured in accordance with JIS K2283:2000.

[0289] (Working cone penetration)

[0290] When the gel composition according to the present embodiment is used as a grease, its worked penetration is preferably 85 to 475, more preferably 130 to 430, further preferably 175 to 385, further preferably 220 to 340, and particularly preferably 265 to 295. If the worked penetration is low, the thickening effect can be improved. The above-mentioned worked penetration can be measured according to the method described in the Examples.

[0291] (Increase in cone penetration)

[0292] When the gel composition according to the present embodiment is used as a grease, the increase in cone penetration is preferably 50 or less, more preferably 45 or less, further preferably 40 or less, and particularly preferably 35 or less. If the increase in cone penetration is small, the shear stability can be improved. The increase in cone penetration is represented by the difference between the mixing stability and the working cone penetration. Both the mixing stability and the working cone penetration can be measured according to the method described in the Examples.

[0293] (Oil separation)

[0294] When the gel composition according to the present embodiment is used as a grease, its oil separation degree is preferably 5.0 mass % or less, more preferably 4.0 mass % or less, and particularly preferably 3.0 mass % or less. If the oil separation degree is low, the oil retention can be improved. In this specification, the oil separation degree can be measured according to the method described in the Examples.

[0295] (Water resistance to washing)

[0296] When the gel composition according to the present embodiment is used as a grease, its water washing resistance is preferably 20.0 mass % or less, more preferably 15.0 mass % or less, and particularly preferably 10.0 mass % or less. If the water washing resistance is low, a gel composition that is not easily softened by water and has poor adhesion can be achieved. In this specification, the water washing resistance can be measured by the method described in the Examples.

[0297] (Viscosity Index)

[0298] When the gel composition according to the present embodiment is used as a lubricating oil, the viscosity index is preferably 100 or more, more preferably 130 or more, and particularly preferably 150 or more, from the viewpoint of easily suppressing viscosity changes due to temperature. In the present specification, the viscosity index can be measured by the method described in the Examples.

[0299] (High temperature high shear viscosity)

[0300] When the gel composition according to the present embodiment is used as a lubricating oil, the high temperature high shear viscosity is preferably 1.5 mPa·s or more, more preferably 2.0 mPa·s or more, and particularly preferably 2.5 mPa·s or more, from the viewpoint of easily improving the protective performance of engines, etc. In the present specification, the high temperature high shear viscosity can be measured by the method described in the Examples.

[0301] (Kinematic viscosity after shear)

[0302] When the gel composition according to this embodiment is used as a lubricating oil, the kinematic viscosity after shearing is preferably 5 mm 2 / sec or more, more preferably 7mm 2 / sec or more, particularly preferably 10 mm2 / sec or more. If the kinematic viscosity after shearing is high, a gel composition that is less likely to undergo molecular cleavage due to shearing can be prepared. In this specification, the kinematic viscosity after shearing can be measured according to the method described in the Examples.

[0303] (MRV viscosity)

[0304] When the gel composition described in this embodiment is used as a lubricating oil, its low temperature pumping viscosity (MRV viscosity (-30°C)) is preferably 200,000 mPa·s or less, more preferably 180,000 mPa·s or less, and particularly preferably 150,000 mPa·s or less. If the MRV viscosity is low, high performance can be exhibited even in a low temperature environment. In this specification, the MRV viscosity can be measured according to the method described in the Examples.

[0305] [Cable filling materials, cables]

[0306] The cable filling material according to the embodiment of the present invention includes the gel composition according to the embodiment of the present invention, and may include only the gel composition. The gel composition according to the embodiment of the present invention has a viscosity that is preferred as a filling material for cables, and can be easily filled into a protective tube or cable when manufacturing the cable, and has a high dropping point, and exhibits a property that the filling material does not leak out from the inside under a wide temperature range even when the protective tube or cable is damaged, and can prevent water from penetrating into the inside, so it is suitable as an internal buffer material for cables such as optical fiber cables and electric wire cables.

[0307] The cable according to the embodiment of the present invention includes the gel composition according to the embodiment of the present invention, and the gel composition is filled between the protection tube and the cable or around the optical fiber core in the cable. As described above, the gel composition of the present invention has sufficient elasticity for protecting the cable, etc., and can be easily filled into the protection tube and the cable, and has a viscosity to such an extent that the filling material does not flow out from the inside when the protection tube and the cable are damaged, and can prevent water from entering the inside even when the protection tube and the cable are damaged. Therefore, the cable can be particularly suitably used as an optical fiber cable.

[0308] [cosmetic]

[0309] The cosmetic according to the embodiment of the present invention includes the gel composition according to the embodiment of the present invention, and may include only the gel composition.

[0310] The gel composition according to the embodiment of the present invention can be used as a cosmetic composition constituting the cosmetic according to the embodiment of the present invention.

[0311] As cosmetics, there can be cited, for example, hair cosmetics such as shampoo, hair styling gel or lotion, blow-dry lotion, styling and shaping agents;

[0312] Skin makeup products such as foundation, eye shadow, blush, concealer, pressed powder and makeup base;

[0313] Lip makeup products such as lipstick, liquid lipstick and lip gloss;

[0314] Cleansing products such as facial cleansing foam and makeup remover oil;

[0315] Cream products such as vaseline cream, hand cream and cream for ultrasonic diagnosis, etc.

[0316] [lubricating oil]

[0317] The lubricating oil according to the embodiment of the present invention includes the gel composition according to the embodiment of the present invention, and may include only the gel composition.

[0318] The gel composition according to the embodiment of the present invention can be used for a lubricating oil composition constituting the lubricating oil according to the embodiment of the present invention. Examples of the lubricating oil include engine oil, automatic transmission fluid, gear lubricating oil, and hydraulic oil.

[0319] [grease]

[0320] The grease according to the embodiment of the present invention includes the gel composition according to the embodiment of the present invention, and preferably includes only the gel composition.

[0321] The gel composition according to the embodiment of the present invention can be used for a grease composition constituting the grease according to the embodiment of the present invention. Examples of the grease include grease for sliding members.

[0322] The sliding member to which the sliding member grease is applied has the above-mentioned grease on its sliding surface, so that the sliding surface slides in the presence of the above-mentioned grease composition. The above-mentioned sliding member is preferably coated with the above-mentioned grease composition on its sliding surface.

[0323] The sliding member preferably includes at least one selected from metal and resin. That is, the material of the sliding member is preferably at least one selected from metal and resin. The sliding member may be a metal sliding member, or a resin sliding member such as plastic, rubber, or a sliding member manufactured using both metal and resin.

[0324] The sliding member is not particularly limited as long as grease is applied to the sliding surface, and examples thereof include door panels, instrument panels, door locks, gears, outboard joints, and the like. joint), inner joint, universal joint, flexible joint, transmission belt tensioner, fixed belt, pressure belt, base (pad), timing belt, conveyor belt, body seal for sunroof, glass run, weather strip, oil seal, packing, wiper blade, scraper, charging roller, developing roller, toner supply roller, transfer roller, heating roller, pressure roller, cleaning plate, paper supply roller, conveying roller, intermediate transfer belt, intermediate transfer drum, heating belt, solenoid valve, electric valve, crankshaft, compressor shaft, sliding bearing, oil pump gear, piston, piston ring, piston pin, gasket, guide rail, seat belt buckle, brake pad, brake pad fixing clip, brake pad, brake insulator, hinge, screw, pressure pad, cylinder, electric cylinder, electric actuator, other sliding members for automobile use, copier use, printer use and industrial machinery use (including semiconductor manufacturing equipment and light emitting device / display manufacturing equipment), etc.

[0325] The above-mentioned grease is also suitable as a grease composition for a rotary sliding member that performs a rotational motion.

[0326] The rotary sliding member is not particularly limited as long as it is accompanied by a rotary motion, and examples thereof include bearings, gears, rotary shafts, belts, heating rollers, and steering rollers.

[0327] In addition, the use of the sliding member is not particularly limited, and can be used for home appliances, ships, railways, aircraft, machinery (including industrial production equipment), structures, automobile repair, automobiles, construction, building materials, fibers, leather, stationery, woodworking, furniture, general merchandise, steel plates, cans, electronic substrates, electronic components, printing and the like. Among these, the sliding member is useful in automobile and industrial machinery applications. That is, the sliding member is preferably an automobile component or an industrial machinery component.

[0328] Likewise, the grease which is one embodiment of the present invention can be suitably used for automobiles and industrial machinery.

[0329] Furthermore, as described above, the grease as one embodiment of the present invention is also useful for reducing noise, and therefore, for example, can be suitably used for a mechanical device or a drive device having an engine, and more specifically, can be suitably used for engine parts.

[0330] [Other uses of the gel composition]

[0331] In addition, the gel composition according to the embodiment of the present invention can be further used for asphalt modifiers, adhesives, binders, resin modifiers, compatibilizers, sealing materials, coating materials, molded products, fibers / nonwoven fabrics, and excavation fluids.

[0332] [Method for producing hydrogenated block copolymer]

[0333] The method for producing a hydrogenated block copolymer according to an embodiment of the present invention comprises the following steps: a first step of performing a polymerization reaction using a polymerization initiator and at least an aromatic vinyl compound, butadiene and isoprene as monomers to obtain a block copolymer including a polymer block (A) and a polymer block (B), wherein the polymer block (A) contains a structural unit derived from the aromatic vinyl compound, and the polymer block (B) contains a structural unit derived from butadiene and a structural unit derived from isoprene; and

[0334] The second step is to hydrogenate the block copolymer.

[0335] Furthermore, in the first step, at least one of the following elements (i) to (vi) is performed.

[0336] (i) The average feed rate when feeding the butadiene and isoprene into the reaction system is set to 50 kg / h / mol or less.

[0337] (ii) The polymerization temperature is set to 55 to 80°C.

[0338] (iii) A vinylating agent is added to the reaction system in an amount of 0.3% by mass or less based on the total mass of the raw material compounds.

[0339] (iv) The time for feeding the butadiene and isoprene into the reaction system is set to 2.5 hours or longer.

[0340] (v) When the amount of the polymerization initiator charged is P (mol) and the amount of the unreacted conjugated diene monomer is Q (mol), Q / P during polymerization of the polymer block (B) is 100 or less.

[0341] (vi) The mass ratio of butadiene and isoprene when they are fed into the reaction system varies depending on the timing of feeding into the reaction system.

[0342] In the first step, by performing at least one of the elements (i) to (vi), the randomness of the structural units derived from butadiene and the structural units derived from isoprene in the polymer block (B) can be easily increased, and the characteristics of the hydrogenated product of the block copolymer in the low temperature region can be improved.

[0343] Specifically, as specified in the above-mentioned element (i), by not excessively increasing the average feed rate of butadiene and isoprene, it is easy to suppress the occurrence of unevenness in the reaction of butadiene and isoprene.

[0344] In addition, as specified in the above-mentioned element (ii), by appropriately raising the polymerization temperature, it is easy to suppress the difference between the reaction rates of butadiene and isoprene from becoming too large. As a result, the randomness of the structural units derived from butadiene in the polymer block (B) is easy to increase.

[0345] Furthermore, as defined in the above-mentioned element (iii), by using a small amount of a vinylating agent, the difference in reaction rate between isoprene and butadiene can be easily reduced, and the randomness of the structural unit derived from butadiene in the polymer block (B) can be easily increased.

[0346] In this case, tetrahydrofuran is preferably used as the vinylating agent used in the element (iii) from the viewpoint that a sharp increase in the amount of vinyl bonds in the obtained block copolymer can be easily avoided by adding the vinylating agent.

[0347] In addition, as specified in the above element (iv), by setting the time for feeding butadiene and isoprene to the reaction system to 2.5 hours or more, the influence caused by the difference in reaction rate between the two monomers can be easily alleviated. As a result, the randomness of the structural units derived from butadiene in the polymer block (B) can be easily increased.

[0348] In addition, as specified in the above-mentioned element (v), when the amount of the polymerization initiator charged is P (mol) and the amount of the unreacted conjugated diene monomer is Q (mol), the polymerization is performed with Q / P being 100 or less, thereby avoiding an excessive increase in the unreacted monomer in the reaction system due to the supply of the conjugated diene compound. Therefore, the preferential reaction of butadiene is suppressed, and as a result, the randomness of the structural unit derived from butadiene in the polymer block (B) is easily increased.

[0349] In addition, as specified in the above-mentioned element (vi), by making the mass ratio of butadiene and isoprene when feeding the reaction system different depending on the timing of feeding into the reaction system, the reaction of the component that is likely to react preferentially can be delayed. Specifically, by making the mass ratio of butadiene having a high reaction rate small in the initial stage of feeding into the reaction system and increasing from the middle to the late stage, the influence of the reaction rate of the reaction with isoprene is alleviated, and as a result, the randomness of the structural unit derived from butadiene in the polymer block (B) is easily increased.

[0350] Hereinafter, the first step and the second step will be described.

[0351] (First process)

[0352] In the first step, the block copolymer can be manufactured by, for example, solution polymerization, emulsion polymerization or solid phase polymerization. Among them, solution polymerization is preferred, and known methods such as anionic polymerization, cationic polymerization, and free radical polymerization can be applied. Among them, anionic polymerization is preferred. In the anionic polymerization method, at least one selected from an aromatic vinyl compound and a conjugated diene compound is added successively in the presence of a solvent, an anionic polymerization initiator and a Lewis base as required to obtain a block copolymer, and a coupling agent is added as required to react.

[0353] Here, from the viewpoint of easily alleviating the influence caused by the difference in reaction rate between butadiene and isoprene, when the charge amount of the polymerization initiator is set to P (mol) and the amount of the unreacted conjugated diene monomer is set to Q (mol) as specified in the above-mentioned element (v), it is preferred to feed the conjugated diene monomer so that Q / P is 100 or less during the polymerization of the polymer block (B).

[0354] Examples of organic lithium compounds that can be used as polymerization initiators for anionic polymerization include methyl lithium, ethyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, and amyl lithium. Examples of dilithium compounds that can be used as polymerization initiators include dilithium naphthalene and dilithium hexylbenzene.

[0355] Examples of the coupling agent include dichloromethane, dibromomethane, dichloroethane, dibromoethane, dibromobenzene, phenyl benzoate, methyldimethoxysilane, trimethoxysilane, tetramethoxysilane, methyltrimethoxysilane, isobutyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane.

[0356] The amount of these polymerization initiators and coupling agents is appropriately determined according to the desired weight average molecular weight of the target block copolymer. Usually, initiators such as alkyl lithium compounds and dilithium compounds are preferably used in a ratio of 0.01 to 0.2 parts by mass relative to a total of 100 parts by mass of monomers such as aromatic vinyl compounds and conjugated diene compounds used in the polymerization, and when a coupling agent is used, it is preferably used in a ratio of 0.001 to 0.8 parts by mass relative to a total of 100 parts by mass of the above-mentioned monomers.

[0357] The solvent is not particularly limited as long as it does not adversely affect the anionic polymerization reaction, and examples thereof include aliphatic hydrocarbons such as cyclohexane, methylcyclohexane, n-hexane, and n-pentane; and aromatic hydrocarbons such as benzene, toluene, and xylene.

[0358] The polymerization reaction is usually carried out at a temperature of 0 to 100°C, preferably 10 to 70°C, for usually 0.5 to 50 hours, preferably 1 to 30 hours.

[0359] From the viewpoint of easily alleviating the influence of the difference in reaction rate between butadiene and isoprene, the polymerization temperature is preferably 55 to 80°C, more preferably 57 to 75°C, and even more preferably 58 to 72°C, as specified in the above-mentioned element (ii).

[0360] From the same viewpoint, as specified in the above element (iv), the time for feeding butadiene and isoprene into the reaction system is set to 2.5 hours or more, more preferably 3 hours or more, further preferably 4 hours or more, and further preferably 5 hours or more.

[0361] Furthermore, by adding a Lewis base as a co-catalyst (vinylating agent) during polymerization, the contents of 3,4-bonds and 1,2-bonds (vinyl bond content) in the polymer block (B) can be increased.

[0362] Examples of the Lewis base include ethers such as dimethyl ether, diethyl ether, tetrahydrofuran, and 2,2-di(2-tetrahydrofuranyl)propane (DTHFP); glycol ethers such as ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether; amines such as triethylamine, N,N,N',N'-tetramethylenediamine, N,N,N',N'-tetramethylethylenediamine (TMEDA), and N-methylmorpholine; sodium or potassium salts of aliphatic alcohols such as sodium tert-butyrate, sodium tert-valerate, or sodium isovalerate; or metal salts such as sodium or potassium salts of alicyclic alcohols such as dialkyl sodium cyclohexanoate and sodium menthate.

[0363] Among the above-mentioned Lewis bases, tetrahydrofuran and DTHFP are preferably used from the viewpoint of impact resistance and thermal stability, and tetrahydrofuran is more preferably used from the viewpoint of easily alleviating the influence caused by the difference in reaction rate between butadiene and isoprene.

[0364] These Lewis bases can be used alone or in combination of two or more.

[0365] The amount of the Lewis base added is determined by the extent to which the vinyl bond amounts of the structural units derived from butadiene and the structural units derived from isoprene constituting the polymer block (B) are controlled. Therefore, the amount of the Lewis base added is not strictly limited, but is usually used in the range of 0.1 to 1,000 mol, preferably 1 to 100 mol, per 1 mol of lithium contained in the alkyl lithium compound or dilithium compound used as a polymerization initiator.

[0366] In addition, when a vinylating agent is used for the purpose of alleviating the influence caused by the difference in reaction rate between butadiene and isoprene, as specified in the above-mentioned element (c), the amount thereof is preferably 0.3% by mass or less, more preferably 0.25% by mass or less, further preferably 0.2% by mass or less, further preferably 0.15% by mass or less, particularly preferably 0.1% by mass or less, and most preferably 0.05% by mass or less, relative to the total mass of the raw material compounds. The lower limit of the amount of the vinylating agent used may be, for example, 0.01% by mass or more, or 0.02% by mass or more.

[0367] Of course, the polymerization reaction may be carried out without adding a Lewis base. In particular, it is preferred not to add a Lewis base in the first step because the glass transition temperature of the hydrogenated product of the block copolymer can be easily lowered.

[0368] Butadiene and isoprene can be supplied to the reaction system at the same mass ratio all the time, or the mass ratio can be varied according to the supply period as specified in the above element (vi). In the former case, it is easy to control when manufacturing the block copolymer, and in the latter case, it is easy to adjust the difference in the reaction rate of the monomers.

[0369] In the polymerization of the polymer block (B) in the first step, as specified in the above-mentioned element (i), from the viewpoint of ensuring the randomness of the structural units derived from butadiene and the structural units derived from isoprene in the polymer block (B), the average feed rate of the conjugated diene compound (hereinafter sometimes referred to as "average diene feed rate") is preferably 50 kg / h / mole or less, more preferably 30 kg / h / mole or less, further preferably 20 kg / h / mole or less, and further preferably 15 kg / h / mole or less relative to 1 mol of the active terminal. The lower limit of the above-mentioned average diene feed rate is not particularly limited, and from the viewpoint of productivity, for example, it is 0.1 kg / h / mole relative to 1 mol of the active terminal. In other words, in the polymerization of the polymer block (B) in the first step, the average feed rate of the above-mentioned conjugated diene compound is preferably 0.1 to 50 kg / h / mole.

[0370] It should be noted that, in this specification, "average diene feed rate" refers to: the mass of the entire conjugated diene compound divided by the time required to feed the entire conjugated diene compound (diene feed time) and the number of moles of active terminals, and its unit is expressed as "kg / h / mole". In addition, the number of moles of active terminals is a value obtained by dividing the amount of monomers (g) used in the polymerization of the polymer block (A) by the weight average molecular weight of the polymer block (A).

[0371] In the first step, after the polymerization has proceeded, an active hydrogen compound such as alcohols, carboxylic acids, or water is added to stop the polymerization reaction.

[0372] (Second process)

[0373] In the second step, for example, a hydrogenation reaction (hydrogenation reaction) is carried out in an inert organic solvent in the presence of a hydrogenation catalyst to obtain a hydrogenated copolymer.

[0374] The hydrogenation reaction can be carried out at a hydrogen pressure of usually 0.1 to 20 MPa, preferably 0.5 to 15 MPa, more preferably 0.5 to 5 MPa, a reaction temperature of usually 20 to 250° C., preferably 50 to 180° C., more preferably 70 to 180° C., and a reaction time of usually 0.1 to 100 hours, preferably 1 to 50 hours.

[0375] As the hydrogenation catalyst, from the viewpoint of suppressing the nuclear hydrogenation of the aromatic vinyl compound and carrying out the hydrogenation reaction of the polymer block (B), for example, Raney nickel; a Ziegler catalyst comprising a combination of a transition metal compound and an alkyl aluminum compound, an alkyl lithium compound, etc.; a metallocene catalyst, etc. From the same viewpoint as above, among them, a Ziegler catalyst is preferred, a Ziegler catalyst comprising a combination of a transition metal compound and an alkyl aluminum compound is more preferred, and a Ziegler catalyst comprising a combination of a nickel compound and an alkyl aluminum compound (Al / Ni-based Ziegler catalyst) is further preferred.

[0376] The hydrogenated block copolymer thus obtained can be obtained by injecting the polymerization reaction liquid into methanol or the like, stirring, filtering, and drying by heating or under reduced pressure, or by injecting the polymerization reaction liquid into hot water together with steam, performing so-called stripping to remove the solvent by azeotropy, and then heating or drying under reduced pressure.

[0377] [Method for producing resin composition]

[0378] The method for producing the resin composition is not particularly limited, and a known method can be used. For example, the resin composition can be produced by mixing the hydrogenated block copolymer of component (a) with the oil component of component (b) using a mixer such as a Henschel mixer, a V-blender, a ribbon blender, a drum blender, or a conical blender, or by melt-kneading using a single screw extruder, a twin screw extruder, a kneader, or the like after mixing.

[0379] When the resin composition further comprises the above-mentioned additives in addition to the components (a) to (d), the above-mentioned additives are mixed with the above-mentioned mixer on the basis of the components (a) and (b), or melt-kneaded by the above-mentioned device after mixing, thereby the above-mentioned resin composition can be manufactured. In addition, a resin composition comprising the components (a) and (b) and optionally comprising the component (d) on the basis of them can also be manufactured in the same manner.

[0380] [Method for producing gel composition]

[0381] The gel composition according to the embodiment of the present invention can be produced by a production method known in the art. For example, it can be produced by mixing a hydrogenated block copolymer as component (α), a base oil (β), and other components as required. The mixing can be performed using a known mixing device.

[0382] More specifically, the hydrogenated block copolymer, the base oil (β), and other components as required are mixed under air or nitrogen at 100 to 200° C. for 0.1 to 10 hours, and if necessary, placed under vacuum, followed by cooling.

[0383] Example

[0384] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples at all.

[0385] [Example 1]

[0386] <Production of Hydrogenated Block Copolymer TPE-1>

[0387] Into a nitrogen-purged and dried pressure vessel were added 50 kg of cyclohexane (solvent) dried over molecular sieve A4 and 0.137 kg of a cyclohexane solution of 10.5 mass % sec-butyllithium as an anionic polymerization initiator (actual amount of sec-butyllithium added: 14.4 g).

[0388] After the temperature in the pressure vessel was raised to 70°C, 1.1 kg of styrene (1) was added and polymerized for 30 minutes, and then 0.012 kg of tetrahydrofuran as a Lewis base was added, and 4.5 kg of butadiene and 5.7 kg of isoprene were added over 5 hours (in other words, the diene feed time was set to 5 hours and the average diene feed rate was set to 9 kg / h / mol), and polymerization was carried out for 1 hour. Thereafter, 1.1 kg of styrene (2) was added and polymerized for 30 minutes, and methanol was added to terminate the reaction, thereby obtaining a reaction solution containing a triblock copolymer of polystyrene-polybutadiene / polyisoprene-polystyrene.

[0389] A Ziegler hydrogenation catalyst composed of nickel octoate and trimethylaluminum was added to the reaction solution under a hydrogen atmosphere, and the reaction was carried out for 5 hours under the conditions of a hydrogen pressure of 1 MPa and 80° C. The reaction solution was naturally cooled and the pressure was released, and then the catalyst was removed by washing with water, and the reaction solution was vacuum dried to obtain a hydrogenated product (TPE-1) of a triblock copolymer of polystyrene-polybutadiene / polyisoprene-polystyrene.

[0390] [Examples 2 to 6]

[0391] <Production of hydrogenated block copolymers TPE-2 to TPE-6>

[0392] Hydrogenated products of triblock copolymers of polystyrene-polybutadiene / polyisoprene-polystyrene (hydrogenated block copolymers TPE-2 to TPE-6) were prepared by the same procedure as in Example 1 except that the raw materials and their amounts were as shown in Table 1. In TPE-6, the polymerization temperature was 60° C., the diene feeding time was 3 hours, and the average diene feeding rate was 41 kg / h / mole. In addition, in TPE-3, tetrahydrofuran was not added when the conjugated diene compound was fed.

[0393] [Examples X7 to X8]

[0394] <Production of hydrogenated block copolymers TPE-7 to TPE-8>

[0395] The raw materials and their amounts were set as shown in Table 1, the polymerization temperature was set to 60°C (Example X7) or 50°C (Example X8), and styrene (2) was not added. Hydrogenated products of polystyrene-polybutadiene / polyisoprene diblock copolymers (hydrogenated block copolymers TPE-7 to TPE-8) were produced in the same manner as in Example 1. It should be noted that the average diene feed rates of Examples X7 to X8 were 14 kg / h / mol and 13 kg / h / mol, respectively.

[0396] [Comparative Examples 1 to 4]

[0397] <Production of hydrogenated block copolymers TPE-1' to TPE-4'>

[0398] Hydrogenated block copolymers TPE-1' to TPE-4' were produced in the same manner as in Example 1 except that the raw materials and their amounts were as shown in Table 1, the diene feeding time was 2 hours, and the polymerization temperature was 50°C.

[0399] It should be noted that the average diene feed rates of Comparative Examples 1 to 4 were 24 kg / h / mol, 19 kg / h / mol, 62 kg / h / mol, and 20 kg / h / mol, respectively. In addition, in Comparative Examples 1 to 3, tetrahydrofuran was not added when the conjugated diene compound was supplied. In Comparative Example 4, only butadiene was used as the conjugated diene compound.

[0400] [Comparative Examples X5 to X7]

[0401] <Production of hydrogenated block copolymers TPE-5' to TPE-7'>

[0402] Hydrogenated block copolymers TPE-5' to TPE-7' were produced by the same procedure as in Example 1 except that the raw materials and their amounts were as shown in Table 1, the polymerization temperature was 50°C (Comparative Examples X5 to X6) or 60°C (Comparative Example X7), and styrene (2) was not added.

[0403] It should be noted that the average diene feed rates of Comparative Examples X5 to X7 were 13 kg / h / mol, 13 kg / h / mol, and 14 kg / h / mol, respectively. In addition, in Comparative Examples X5 to X7, tetrahydrofuran was not added when the conjugated diene compound was supplied. In Comparative Example X5, only isoprene was used as the conjugated diene compound.

[0404] Table 1

[0405]

[0406] Table 1 (continued)

[0407]

[0408] <Physical Properties of Hydrogenated Block Copolymer>

[0409] The physical properties of hydrogenated block copolymers TPE-1 to TPE-8 and TPE-1' to TPE-7' were measured according to the following measurement methods. The results are shown in Table 2 together with the composition of each hydrogenated block copolymer. It should be noted that "-" in Table 2 means that the hydrogenated block copolymer cannot be measured because it is impossible to mold it. In addition, the hydrogenated block copolymer TPE-5' of Comparative Example X5 cannot detect the crystallization peak, so the following "crystallization temperature" and "crystallization heat" cannot be measured. Therefore, it is recorded as "-" in the corresponding parts of Table 2 and in the "5.8x·100000-y" column. * In addition, in the hydrogenated block copolymer TPE-5', the polymer block (B) does not have a structural unit derived from butadiene, and the following "1,4Bd chain ratio" cannot be measured. Therefore, the corresponding part in Table 2 is recorded as "- ** ”.

[0410] (Contents of polymer block (A) and polymer block (B))

[0411] Dissolve the hydrogenated block copolymer in CDCl3 and perform 1 1H-NMR measurement [Apparatus: "AVANCE400 Nanobay" (manufactured by Bruker Corporation), measurement temperature: 30 °C]. Calculate the content of polymer block (A) based on the peak intensity derived from styrene, and calculate the content of polymer block (B) by subtracting the content of polymer block (A) from 100 mass%.

[0412] (Amount of vinyl bonding in polymer block (B))

[0413] Dissolve the block copolymer before hydrogenation in CDCl3 and perform 1 1H-NMR measurement [Apparatus: "AVANCE400 Nanobay" (manufactured by Bruker Corporation), measurement temperature: 30 °C]. Moreover, calculate the amount of vinyl bonding based on the ratio of the peak areas corresponding to the 3,4-bonding unit and 1,2-bonding unit in the isoprene structural unit, and the 1,2-bonding unit in the butadiene structural unit to the total peak area derived from the structural units of butadiene and isoprene.

[0414] (Hydrogenation rate of polymer block (B))

[0415] Dissolve the hydrogenated block copolymer in CDCl3 and perform 1 1H-NMR measurement [Apparatus: "AVANCE400 Nanobay" (manufactured by Bruker Corporation), measurement temperature: 30 °C], and calculate the hydrogenation rate based on the ratio of the peak area of the residual olefins derived from butadiene or isoprene and the peak area of the hydrogenated butadiene and hydrogenated isoprene.

[0416] (Weight-average molecular weight (Mw))

[0417] Determine the polystyrene-reduced weight-average molecular weight (Mw) of the hydrogenated block copolymer by gel permeation chromatography (GPC) under the following conditions. Additionally, by the same measurement, determine the Mw of polymer block (A) based on the peak derived from the initially deactivated polymer block (A).

[0418] <<GPC Measurement Apparatus and Measurement Conditions>>

[0419] · Apparatus: GPC apparatus "HLC-8020" (manufactured by Tosoh Corporation)

[0420] · Separation column: Two "TSKgel G4000HX" manufactured by Tosoh Corporation are connected in series.

[0421] ·Eluent: Tetrahydrofuran

[0422] Eluent flow rate: 0.7mL / min

[0423] Sample concentration: 5mg / 10mL

[0424] Column temperature: 40°C

[0425] Detector: Differential refractive index (RI) detector

[0426] Standard curve: Prepared using standard polystyrene

[0427] (Tan δ and shear storage modulus G' at -40°C of hydrogenated block copolymer)

[0428] For the following measurements, the hydrogenated block copolymers obtained in Examples and Comparative Examples were pressed for 3 minutes at a temperature of 230° C. and a pressure of 10 MPa to prepare a monolayer sheet having a thickness of 1.0 mm. The monolayer sheet was cut into a disk shape to prepare a test piece.

[0429] In the measurement, a strain-controlled dynamic viscoelasticity device "ARES-G2" (manufactured by TA Instruments) having a circular plate diameter of 8 mm was used as a parallel plate vibrating flow meter in accordance with JIS K7244-10 (2005).

[0430] The gap between the two flat plates was completely filled with the test piece, and the sample was vibrated in shear mode at a strain of 1% and a frequency of 1 Hz. The temperature was raised from -80°C to 0°C at a constant rate of 3°C / min. The maximum value (peak top intensity) of the peak intensity of tanδ of the hydrogenated block copolymer at the measuring temperature of -80 to 0°C, the temperature at which the maximum value was obtained (peak top temperature), and the shear storage modulus G' of the hydrogenated block copolymer at -40°C were determined.

[0431] (Glass transition temperature (Tg))

[0432] The Tg of the hydrogenated block copolymer was measured by using DSC250 manufactured by TA Instruments, by heating from -100°C to +350°C at 10°C / min, and the shift position of the baseline of the DSC curve (specifically, the intersection of the line segment of the midpoint of the baseline before and after the specific heat change and the DSC curve) was defined as Tg.

[0433] (Crystallization temperature and crystallization heat)

[0434] The crystallization temperature and the heat of crystallization of the hydrogenated block copolymer were obtained as follows: according to JIS K7121 (2012) and JIS K7122 (2012), using DSC250 manufactured by TA Instruments, the temperature was changed in the order of the following heating step 1, cooling step, and heating step 2, the crystallization temperature was obtained from the peak temperature of the DSC curve obtained in the cooling step, and the heat of crystallization was obtained from the peak area. In addition, the peak area was calculated by using a straight line passing through the two points of the peak temperature + 80°C and the peak temperature + 50°C in the DSC curve as a baseline.

[0435] Heating step 1: Heating from 40°C to 180°C at a heating rate of 10°C / min

[0436] Cooling process: Cooling from +180°C to -100°C at a cooling rate of 10°C / min

[0437] Heating step 2: Heating from -100°C to +180°C at a heating rate of 10°C / min

[0438] (5.8x / 100,000-y)

[0439] The weight average molecular weight of the hydrogenated block copolymer measured in the above-described manner is defined as x, and the crystallization temperature of the hydrogenated block copolymer is defined as y (° C.), and the value of “5.8x / 100,000-y” is calculated.

[0440] (1,4-bond ratio of hydrogenated butadiene)

[0441] For the hydrogenated block copolymers obtained in each embodiment and comparative example, the reverse gated decoupling 13 In the C-NMR measurement, the ratio of the peak appearing at 29.2 ppm among the peaks derived from 1,4-bonds of hydrogenated butadiene obtained by the measurement was calculated and defined as the chain ratio of 1,4-bonds of hydrogenated butadiene (1,4Bd chain ratio).

[0442] (Tensile strength and tensile elongation at break)

[0443] The hydrogenated block copolymer obtained in each example and comparative example was pressed for 3 minutes at a temperature of 230°C and a pressure of 10 MPa to prepare a single-layer sheet with a thickness of 1.0 mm. The sheet was punched into a JIS No. 3 dumbbell-shaped test piece, and the tensile strength and tensile elongation at break were measured according to JIS K 6251 (2017). The higher the values ​​of tensile strength and tensile elongation at break, the better the tensile properties.

[0444] Table 2

[0445]

[0446]

[0447] Table 2 (continued)

[0448]

[0449] As shown in Table 2, in the hydrogenated block copolymers of Examples 1 to 6 and Examples X7 to X8, the structural units derived from conjugated diene compounds of the polymer block (B) have structural units derived from butadiene and structural units derived from isoprene, and do not have structural units derived from farnesene. In addition, the glass transition temperature of the hydrogenated block copolymer is below -50°C. Moreover, the weight average molecular weight x of the hydrogenated block copolymer and the crystallization temperature y (°C) of the hydrogenated block copolymer satisfy the relationship of 5.8x / 100,000-y>17. In other words, the hydrogenated block copolymers of Examples 1 to 6 and Examples X7 to X8 satisfy the above conditions (1) to (3). It can also be seen that the hydrogenated block copolymers of Examples 1 to 6 have low crystallization temperatures and heat of crystallization, and have good softness and rubber elasticity in the low temperature region.

[0450] It is also found that the hydrogenated block copolymers of Examples 1 to 5 that also satisfy the conditions (I) to (III) have slightly low values ​​of shear storage modulus G' at -40°C and 1 Hz, and exhibit excellent rubber elasticity and flexibility in a low temperature range.

[0451] The hydrogenated block copolymers of Examples X7 to X8 have a diblock polymer structure, and have lower values ​​of tensile strength and tensile elongation at break than the hydrogenated block copolymers of Examples 1 to 6. However, it is found that, when compared with Comparative Examples X7 and X6, which have a diblock polymer structure but do not satisfy Condition (3), the values ​​of tensile elongation at break are larger, the values ​​of tensile strength are equal to or higher, and the values ​​of shear storage modulus G' at -40°C and 1 Hz are lower.

[0452] On the other hand, it is found that the hydrogenated block copolymers of Comparative Examples 1 and 2, which satisfy the above conditions (1) and (2) but not the condition (3), and satisfy the above conditions (I) and (II) but not the condition (III), have smaller tensile elongation at break than the hydrogenated block copolymers of Examples 1 to 5.

[0453] In addition, when compared with the hydrogenated products of the block copolymers of Examples 1 and 2 having the same content of the polymer block (A), the hydrogenated product of the block copolymer of Comparative Example 1 has a larger value of the shear storage modulus G' at -40°C and 1 Hz. In other words, it is found that the rubber elasticity and flexibility in the low temperature region are inferior to those of the hydrogenated products of the block copolymers of Examples 1 and 2.

[0454] In addition, when compared with the hydrogenated products of the block copolymers of Examples 3 to 5 having the same content of the polymer block (A), the hydrogenated products of the block copolymers of Comparative Examples 2 and 4 have a lower peak strength of tan δ and a larger value of the shear storage modulus G' at -40°C and 1 Hz. In other words, it can be seen that the rubber elasticity and flexibility in the low temperature region are inferior to those of the hydrogenated products of the block copolymers of Examples 3 to 5.

[0455] It should be noted that the hydrogenated block copolymer of Example 6, which satisfies the above conditions (1) to (3), conditions (I) and (II) but does not satisfy condition (III), and the hydrogenated block copolymer of Comparative Example 3, which satisfies the above conditions (1) and (2) but does not satisfy condition (3), and satisfies the above conditions (I) and (II) but does not satisfy condition (III), lacks moldability and cannot be molded. Therefore, the peak temperature of tan δ, the peak strength of tan δ, the shear storage modulus G' at -40°C and 1 Hz, the tensile strength, and the tensile elongation at break could not be measured.

[0456] Among them, it is clear from the comparison between the hydrogenated block copolymer of Example 6 and the hydrogenated block copolymer of Comparative Example 3 that the former has lower crystallization temperature and heat of crystallization than the latter, and has better flexibility and rubber elasticity in a low temperature region. In addition, as shown in Table 3, it is known that when the hydrogenated block copolymers are added to the oil component to prepare a resin composition, the tensile strength of the former becomes higher.

[0457] [Example 7] and [Comparative Example 5]

[0458] The hydrogenated block copolymers and oils obtained in the above Examples and Comparative Examples were prepared according to the proportions shown in Table 3. These materials were left at 110° C. for 90 minutes and then kneaded at 110° C. and 70 rpm for 5 minutes using Labo Plastomill 10S100 (manufactured by Toyo Seiki Seisaku-sho, Ltd.) to obtain a resin composition.

[0459] 〈Oil-1〉

[0460] DIANA PROCESS OIL PW-32 (Parallane oil, manufactured by Idemitsu Kosan Co., Ltd.)

[0461] (Tensile Strength)

[0462] The obtained resin composition was pressed for 2 minutes at a temperature of 160°C and a pressure of 2 MPa to prepare a single-layer sheet with a thickness of 2.0 mm. The sheet was punched into a JIS No. 3 dumbbell-shaped test piece, and the tensile strength was measured under the conditions of a clamp distance of 10 mm, a clamp pressure of 0.25 MPa, and a tensile speed of 500 mm / min according to JIS K6251 (2017). The results are shown in Table 3.

[0463] (Oil retention rate)

[0464] The obtained resin composition was pressed at a temperature of 160° C. and a pressure of 2 MPa for 2 minutes to prepare a single-layer sheet having a thickness of 2.0 mm. The sheet was punched into pieces having a diameter of Both sides were sealed with filter paper (ADVANTEC TOYO Co., Ltd., ADVANTEC No. 5C ) and further sandwiched the two sides with glass plates, and the object thus obtained was used as a sample. The sample was placed in an environment of 23°C and -30°C, and the filter paper was replaced with a new one every 7 days for 28 days. The oil retention rate ((M1 / M0)×100) was calculated based on the weight M0 of the resin composition sheet before the test and the weight M1 of the resin composition sheet after 28 days. The results are shown in Table 3.

[0465] Table 3

[0466]

[0467]

[0468] As shown in Table 3, the resin composition of Example 7 exhibited higher tensile strength than the resin composition of Comparative Example 5, and also exhibited higher oil retention at 23°C and -30°C than the resin composition of Comparative Example 5. In other words, it was found that the resin composition obtained using the hydrogenated block copolymer (TPE-6) satisfying the above conditions (1) to (3) exhibited better mechanical properties and was excellent in oil retention at room temperature and low temperature than the resin composition obtained using the hydrogenated block copolymer (TPE-3') satisfying the above conditions (1) and (2) but not satisfying the condition (3).

[0469] [Examples 8 to 9] and [Comparative Example 6]

[0470] The hydrogenated block copolymers obtained in the above Examples and Comparative Examples and the following resins were prepared according to the proportions shown in Table 4. These materials were kneaded at 200° C. and 70 rpm for 3 minutes using Labo Plastomill 10S100 (manufactured by Toyo Seiki Seisaku-sho, Ltd.) to obtain a resin composition.

[0471] 〈PP-1〉

[0472] PRIMEPOLYPRO J107G (homopolymer polypropylene, manufactured by Prime Polymer)

[0473] 〈POE-1〉

[0474] ENGAGE8200 (polyolefin elastomer, manufactured by Dow Chemical Co.)

[0475] 〈HDPE-1〉

[0476] ·SHE150 (high-density polyethylene, manufactured by Braskem)

[0477] (Tensile properties)

[0478] Using a desktop injection molding machine ("Mini-Jet Pro", manufactured by Thermo Fisher Scientific), each resin composition obtained was injection molded into an ISO527-2-1BA dumbbell test piece as a test piece. After the test piece was stored at 23°C for 16 hours, the Autograph manufactured by Shimadzu Corporation was used for measurement in accordance with JIS K 7161 (2014), thereby measuring the tensile elastic modulus (23°C), the yield stress (23°C) and the tensile elongation at break (23°C). In addition, after the test piece was stored at -20°C for 16 hours, the same measurement was performed to measure the yield stress (-20°C) and the tensile elongation at break (-20°C). The results are shown in Table 4.

[0479] (Charpy impact strength)

[0480] Each resin composition was injection molded into a test piece of 10 mm in length × 80 mm in width × 4 mm in thickness using a desktop injection molding machine ("Mini-Jet Pro", manufactured by Thermo Fisher Scientific), and notched according to JIS K 7111-1 (2012). After the test piece was stored at 23°C for 16 hours, the Charpy impact strength (23°C) was measured using an impact strength tester. The results are shown in Table 4.

[0481] Table 4

[0482]

[0483] As shown in Table 4, the resin compositions of Examples 8 and 9 showed higher tensile elongation at break (23°C) than the resin composition of Comparative Example 6. In addition, the resin composition of Example 8 showed higher tensile elongation at break (-20°C) than the resin composition of Comparative Example 6. Furthermore, the resin compositions of Examples 8 and 9 showed higher impact strength than the resin composition of Comparative Example 6. In other words, it can be seen that the resin compositions obtained using hydrogenated block copolymers (TPE-1, TPE-2) satisfying the above conditions (1) to (3) and conditions (I) to (III) have improved tensile elongation at break and impact strength compared to the resin composition obtained using the hydrogenated block copolymer (TPE-1') satisfying the above conditions (1) and (2) but not satisfying the condition (3), and satisfying the above conditions (I) and (II) but not satisfying the condition (III).

[0484] [Examples 10 to 11] and [Comparative Examples 7 to 8]

[0485] The hydrogenated block copolymers obtained in the above Examples and Comparative Examples and the above HDPE-1 were kneaded at 200° C. and 70 rpm for 3 minutes using Labo Plastomill 10S100 (manufactured by Toyo Seiki Seisaku-sho) according to the proportions shown in Table 5 to obtain a resin composition.

[0486] (Flexural modulus and flexural strength)

[0487] The obtained resin compositions were injection molded using an injection molding machine ("EC75SX", manufactured by Toshiba Machine Co., Ltd.) to produce JIS multi-purpose test piece A1. The central portion (length 80 mm × width 10 mm × thickness 4 mm) was used to perform a bending strength test according to JIS K7171 (ISO 178) using a universal testing machine (manufactured by INSTRON, model 5566) to measure the bending elastic modulus [MPa] and the bending strength [MPa]. The results are shown in Table 5.

[0488] (Melt flow rate)

[0489] For each of the obtained resin compositions, the outflow rate (g / 10 min) of the sample was measured using a melt indexer under the conditions of a temperature of 23° C. and a load of 2.16 kg in accordance with JIS K 7210:2014.

[0490] (Charpy impact strength)

[0491] The Charpy impact strength (23°C) of each resin composition obtained was measured in the same manner as above. In addition, the Charpy impact strength (0°C) and Charpy impact strength (-23°C) were measured in the same manner except that the measurement temperature was 0°C and -20°C. The results are shown in Table 5.

[0492] Table 5

[0493]

[0494]

[0495] As shown in Table 5, the resin composition of Example 10 obtained using TPE-7 has the same or higher values ​​of flexural modulus, flexural strength and MFR as the resin composition of Comparative Example 7 obtained using TPE-5', and has significantly improved Charpy impact strength in the temperature range from near room temperature to low temperature.

[0496] The resin composition of Example 11 obtained using TPE-8 also has the same or higher flexural modulus, flexural strength and MFR values ​​as the resin composition of Comparative Example 8 obtained using TPE-6′, and has improved Charpy impact strength in the temperature range from near room temperature to low temperatures.

[0497] These results show that the resin compositions obtained using hydrogenated block copolymers satisfying the above conditions (1) to (3) and conditions (I) to (III) (TPE-7, TPE-8) have bending properties and flowability that are equal to or better than those of a resin composition obtained using a hydrogenated block copolymer (TPE-5') that does not satisfy the conditions (1), (3), (I) and (III) and a resin composition obtained using a hydrogenated block copolymer (TPE-6') that does not satisfy the conditions (3) and (III), and that the impact resistance can be improved over a wide temperature range from near room temperature to low temperatures.

[0498] [Examples 12 to 13] and [Comparative Examples 9 to 10]

[0499] The hydrogenated block copolymer obtained in the above-mentioned examples and comparative examples and the following oil components were prepared in the proportions shown in Table 6. The hydrogenated block copolymer and the base oil were mixed at 150°C for 3 hours using a THREE-ONE MOTOR manufactured by Shinto Chemical Co., Ltd. under nitrogen, and then cooled to room temperature to obtain a precursor mixture. The obtained precursor mixture was mixed with lithium grease at 80 to 90°C for 30 minutes using a stainless steel spoon. Thereafter, the mixture was cooled to room temperature to obtain a gel composition.

[0500] <Lithium grease>

[0501] MONOTARO Co., Ltd., "MONOTARO (registered trademark) lithium grease" (cone penetration number: No. 2, thickener: lithium soap, thickener content: 10% by mass, base oil: mineral oil, base oil content: 85-90% by mass)

[0502] <Base oil>

[0503] ・SAMIC (registered trademark) G-150 (Group II mineral oil) manufactured by Sanwa Chemical Industries, Ltd.

[0504] (Working penetration and increased penetration)

[0505] The cone penetration (worked cone penetration) of each obtained gel composition was measured according to Item 7 of JIS K 2220:2013. In addition, the mixing stability of each obtained gel composition was measured according to Item 15 of JIS K2220:2013, and the difference between the mixing stability and the worked cone penetration was defined as the cone penetration increase. The results are shown in Table 6.

[0506] (Oil separation)

[0507] The oil release rate of each of the obtained gel compositions was measured in accordance with Item 11 of JIS K2220:2013. The results are shown in Table 6.

[0508] (Water resistance to washing)

[0509] The water resistance of each of the obtained gel compositions was measured in accordance with Item 16 of JIS K2220:2013. The results are shown in Table 6.

[0510] Table 6

[0511]

[0512] As shown in Table 6, compared with the gel composition of Comparative Example 9 obtained by using the hydrogenated block copolymer TPE-6' which does not satisfy the condition (3), the gel composition of Example 12 obtained by using the hydrogenated block copolymer TPE-8 which satisfies the conditions (1) to (3) has a lower worked penetration and a suppressed increase in penetration, although the oil release rate and water resistance are equivalent, and has characteristics more suitable for a gel composition for grease.

[0513] Furthermore, as shown in Table 6, the gel composition of Example 13 obtained by using the hydrogenated block copolymer TPE-7 satisfying the conditions (1) to (3) has a lower worked penetration and a lower increase in penetration than the gel composition of Comparative Example 10 obtained by using the hydrogenated block copolymer TPE-7' not satisfying the condition (3), although the oil release rate and water resistance are equivalent, and the increase in penetration is also suppressed, and has characteristics more suitable for a gel composition for grease.

[0514] These results are presumably because the hydrogenated block copolymer TPE-8 satisfying conditions (1) to (3) has improved compatibility with oil, and therefore has improved thickening effect at temperatures above room temperature.

[0515] [Examples 14 to 15] and [Comparative Examples 11 to 12]

[0516] The hydrogenated block copolymers obtained in the above examples and comparative examples and the following components were prepared according to the proportions shown in Table 7. These materials were mixed at 150° C. for 3 hours using a THREE-ONE MOTOR manufactured by Shinto Chemical Co., Ltd. under nitrogen. Thereafter, the mixture was cooled to room temperature to obtain a gel composition.

[0517] <Base oil>

[0518] ・SAMIC (registered trademark) G-150 (Group II mineral oil) manufactured by Sanwa Chemical Industries, Ltd.

[0519] <Pour Point Depressant>

[0520] VISCOPLEX 1-330 manufactured by EVONIK

[0521] (Kinematic viscosity)

[0522] The kinematic viscosity of each of the obtained gel compositions at 40° C. and 100° C. was measured in accordance with JIS K2283:2000. The results are shown in Table 7.

[0523] (Viscosity Index)

[0524] The viscosity index of each of the obtained gel compositions was measured in accordance with JIS K2283:2000. The results are shown in Table 7.

[0525] (High temperature and high shear viscosity at 150°C)

[0526] The high-temperature high-shear viscosity of each gel composition obtained at 150° C. was measured or calculated in accordance with the Institute of Petroleum's petroleum test-related standard JPI-5S-36. The results are shown in Table 7.

[0527] (Kinematic viscosity after shear)

[0528] The kinematic viscosity (100° C.) of each gel composition obtained after shearing was measured by a diesel injector method in accordance with the Institute of Petroleum's petroleum test related standard JPI-5S-29.

[0529] (MRV viscosity at -30°C)

[0530] The low temperature pumping viscosity (MRV viscosity (-30°C)) of each of the obtained gel compositions at -30°C was measured in accordance with ASTM D 4684. The results are shown in Table 7.

[0531] Table 7

[0532]

[0533] As shown in Table 7, the gel composition of Example 14 obtained using the hydrogenated block copolymer TPE-8 satisfying the conditions (1) to (3) has the same values ​​of kinematic viscosity at 40°C and 100°C, viscosity index, high-temperature high-shear viscosity, and kinematic viscosity after shearing as the gel composition of Comparative Example 11 obtained using the hydrogenated block copolymer TPE-6' not satisfying the condition (3), but has a much lower MRV viscosity at -30°C. In addition, the gel composition of Example 15 obtained using the hydrogenated block copolymer TPE-7 satisfying the conditions (1) to (3) has the same values ​​of kinematic viscosity at 40°C and 100°C, viscosity index, high-temperature high-shear viscosity, and kinematic viscosity after shearing as the gel composition of Comparative Example 12 obtained using the hydrogenated block copolymer TPE-7' not satisfying the condition (3), but has a much lower MRV viscosity at -30°C. Therefore, the gel compositions of Examples 14 and 15 have characteristics that are advantageous for gel compositions for engine oils having excellent low-temperature characteristics.

[0534] [Example 16] and [Comparative Example 13]

[0535] The hydrogenated block copolymers obtained in the above Examples and Comparative Examples and the following oil components were prepared in the proportions shown in Table 8. These materials were mixed at 150° C. for 3 hours using a THREE-ONE MOTOR manufactured by Shinto Chemical Co., Ltd. under nitrogen. Thereafter, the mixture was cooled to room temperature to obtain a gel composition.

[0536] <Base oil>

[0537] ・SAMIC (registered trademark) G-150 (Group II mineral oil) manufactured by Sanwa Chemical Industries, Ltd.

[0538] (Viscosity)

[0539] A rheometer (R / S+RHEOMETER manufactured by Brookfield) was used to measure the flow rate at 25°C for 50 seconds. -1 The viscosity of each gel composition was measured under the shear rate conditions (25°C, 50 sec -1In more detail, about 30 mL of the gel composition was placed in a sample chamber (MB3-25F manufactured by Brookfield), installed in a rheometer body equipped with a measuring axis (CC3-25 manufactured by Brookfield), and the rheometer was heated at 25°C for 1 s. -1 The shear rate was measured for 300 seconds and stabilized. Next, (1) the shear rate was increased from 1 s to -1 Increase to 50s -1 After that, it takes 120 seconds to go from 50s -1 Reduced to 1s -1 Then, (2) the shear rate was increased from 1s to -1 Increase to 50s -1 After that, it takes 120 seconds to go from 50s -1 Reduced to 1s -1 Then, (3) it took 120 seconds to reduce the shear rate from 1s -1 Increase to 50s -1 After that, it takes 120 seconds to go from 50s -1 Reduced to 1s -1 Using the method (3) above, it takes 120 seconds to reduce the shear rate from 1s -1 Increase to 50s - 1 The 50s obtained in the measurement of the process -1 The viscosity of the gel composition was taken as the viscosity under the shear rate conditions (25°C, 50 sec -1 ). The results are shown in Table 8.

[0540] Table 8

[0541]

[0542] As shown in Table 8, the gel composition of Example 16 and the gel composition of Example 17 obtained by using the hydrogenated block copolymer TPE-8 satisfying the conditions (1) to (3) have higher viscosity at 25°C than the gel composition of Comparative Example 13 obtained by using the hydrogenated block copolymer TPE-6' not satisfying the condition (3), and have favorable properties for cable filling materials. It is presumed that this is because the hydrogenated block copolymer TPE-8 satisfying the conditions (1) to (3) has improved compatibility with oil, and therefore the thickening effect is improved at a temperature above room temperature.

[0543] [Example 17] and [Comparative Example 14]

[0544] The hydrogenated block copolymers obtained in the above examples and comparative examples and the following components were prepared according to the proportions shown in Table 9. These materials were mixed at 150° C. for 3 hours using a THREE-ONE MOTOR manufactured by Shinto Chemical Co., Ltd. under nitrogen. Thereafter, the mixture was cooled to room temperature to obtain a gel composition.

[0545] <pao>

[0546] · Poly-α-olefin (manufactured by INEOS Oligomers, Durasyn 166)

[0547] (Viscosity)

[0548] The viscosity of each gel composition obtained was measured in the same manner as above (25°C, 50 sec -1 ). The results are shown in Table 9.

[0549] Table 9

[0550]

[0551] As shown in Table 9, the gel composition of Example 17 obtained using the hydrogenated block copolymer TPE-8 satisfying the conditions (1) to (3) has a higher viscosity at 25°C than the gel composition of Comparative Example 14 obtained using the hydrogenated block copolymer TPE-6' not satisfying the condition (3), and has advantageous properties for a cosmetic gel composition. This is presumably because the hydrogenated block copolymer TPE-8 satisfying the conditions (1) to (3) has improved compatibility with oil, and therefore has improved thickening effect at room temperature or above.

[0552] Industrial Applicability

[0553] The hydrogenated product of the block copolymer of the present invention and the resin composition can be used for automobile housings, various parts mounted in automobiles, and housings thereof. In addition, the block copolymer can be used in the field of household appliances, such as televisions, various recorders such as blue-ray recorders and HDD recorders, projectors, game consoles, digital cameras, home video recorders, antennas, speakers, electronic dictionaries, IC recorders, FAX, copiers, telephones, doorbells, rice cookers, microwave ovens, ovens, refrigerators, dishwashers, dishwashing machines, IH cooking heaters, hot plates, vacuum cleaners, washing machines, chargers, sewing machines, irons, dryers, electric bicycles, air purifiers, water purifiers, electric toothbrushes, lighting equipment, air conditioners, outdoor units of air conditioners, dehumidifiers, humidifiers, and various electrical products.

[0554] In addition, the gel composition of the present invention is useful for materials such as cable filling materials used in cables such as optical fiber cables, grease, engine oil, cosmetics, lubricating oil, asphalt modifiers, adhesives, binders, resin modifiers, compatibilizers, sealing materials, coating materials, molded products, fibers and nonwoven fabrics, and mining fluids.< / pao>

Claims

1. A hydrogenated product of a block copolymer, comprising a polymer block (A) and a polymer block (B), wherein the polymer block (A) contains a structural unit derived from an aromatic vinyl compound, and the polymer block (B) contains a structural unit derived from a conjugated diene compound, wherein the hydrogenated product of the block copolymer satisfies the following conditions (1) to (3), (1) The structural unit derived from the conjugated diene compound of the polymer block (B) includes a structural unit derived from butadiene and a structural unit derived from isoprene, and does not include a structural unit derived from farnesene; (2) The glass transition temperature of the hydride of the block copolymer is below -50°C; (3) When the weight average molecular weight of the hydrogenated product of the block copolymer is x and the crystallization temperature of the hydrogenated product of the block copolymer is y (° C.), the relationship of 5.8x / 100,000-y>17 is satisfied.

2. The hydrogenated block copolymer according to claim 1, wherein The content of the polymer block (A) in the hydrogenated product of the block copolymer is 5 to 70% by mass.

3. The hydrogenated block copolymer according to claim 2, wherein The content of the polymer block (A) in the hydrogenated product of the block copolymer is 8 to 33% by mass.

4. The hydrogenated product of the block copolymer according to any one of claims 1 to 3, wherein The amount of vinyl bonds in the polymer block (B) is 25 mol% or less.

5. The hydrogenated block copolymer according to claim 4, wherein The amount of vinyl bonds in the polymer block (B) is 18 mol% or less.

6. The hydrogenated product of the block copolymer according to any one of claims 1 to 5, wherein The content of the structural unit derived from butadiene in the polymer block (B) is 10 to 90 mol%.

7. The hydrogenated block copolymer according to claim 6, wherein The content of the structural unit derived from butadiene in the polymer block (B) is 15 to 70 mol%.

8. The hydrogenated block copolymer according to claim 6, wherein The content of the structural unit derived from butadiene in the polymer block (B) is 30 to 85 mol%.

9. The hydrogenated product of the block copolymer according to any one of claims 1 to 8, wherein The crystallization heat of the hydrogenated product of the block copolymer is 20 J / g or less.

10. The hydrogenated product of the block copolymer according to any one of claims 1 to 9, wherein The hydrogenated block copolymer has a weight average molecular weight of 30,000 to 500,000.

11. The hydrogenated product of the block copolymer according to any one of claims 1 to 10, wherein The hydrogenation rate of the polymer block (B) is 90 mol% or more.

12. The hydrogenated product of the block copolymer according to any one of claims 1 to 11, further satisfying the following condition (4): (4) Decoupling through anti-gating 13 The chain ratio of 1,4-bonds of hydrogenated butadiene represented by the ratio of the peak appearing at 29.2 ppm among the peaks derived from 1,4-bonds of hydrogenated butadiene obtained by C-NMR measurement was less than 50%.

13. The hydrogenated product of the block copolymer according to any one of claims 1 to 12, wherein The tensile elongation at break measured in accordance with JIS K 6251 (2017) is 300% or more.

14. The hydrogenated product of the block copolymer according to any one of claims 1 to 13, wherein The shear storage modulus G′ at −40° C. measured by a complex shear viscosity test at a frequency of 1 Hz in accordance with JIS K7244-10 (2005) is 200 MPa or less.

15. A resin composition, wherein As component (a), a hydrogenated product of the block copolymer according to any one of claims 1 to 14 is contained, and As component (b), at least one oil component selected from mineral oil, vegetable oil and ethylene / α-olefin copolymer oligomer is contained, The content ratio (a) / (b) of the component (a) and the component (b) is 1 / 99 to 99 / 1 in terms of mass ratio.

16. A resin composition, wherein A hydrogenated product of the block copolymer according to any one of claims 1 to 14 is contained as component (a); and As component (c), at least one selected from polyethylene, polypropylene, styrene resins, polyphenylene ether, polyester resins, polycarbonate, polyacetal, polyamide, polyarylene sulfide, polyarylate, polyimide, polyetheretherketone and liquid crystal polyester is contained, The content ratio (a) / (c) of the component (a) and the component (c) is 1 / 99 to 99 / 1 in terms of mass ratio.

17. A gel composition comprising a base oil (β) and a hydrogenated product of the block copolymer according to any one of claims 1 to 14 as a component (α).

18. A cable filling material comprising the gel composition according to claim 17.

19. A cable comprising the gel composition of claim 17.

20. A cosmetic comprising the gel composition according to claim 17.

21. A lubricating oil comprising the gel composition according to claim 17.

22. A lubricating grease comprising the gel composition of claim 17.

23. The method for producing a hydrogenated product of a block copolymer according to any one of claims 1 to 14, comprising the following steps: A first step of performing a polymerization reaction using a polymerization initiator and at least an aromatic vinyl compound, butadiene and isoprene as monomers to obtain a block copolymer including a polymer block (A) containing a structural unit derived from the aromatic vinyl compound and a polymer block (B) containing a structural unit derived from the butadiene and a structural unit derived from the isoprene; and The second step is to hydrogenate the block copolymer. In the first step, at least one of the following elements (i) to (vi) is performed. (i) the average feed rate of the butadiene and isoprene when feeding the reaction system is set to 50 kg / h / mole or less; (ii) setting the polymerization temperature to 55 to 80°C; (iii) adding a vinylating agent in an amount of 0.3% by mass or less relative to the total mass of the raw material compounds to the reaction system; (iv) the time for feeding the butadiene and isoprene into the reaction system is set to be more than 2.5 hours; (v) when the amount of the polymerization initiator charged is P (mol) and the amount of the unreacted conjugated diene monomer is Q (mol), Q / P during the polymerization of the polymer block (B) is 100 or less; (vi) The mass ratio of butadiene and isoprene when they are fed into the reaction system varies depending on the timing of feeding into the reaction system.

Citation Information

Patent Citations

  • Hydrogenated block copolymer and method for producing same

    WO2013183570A1

  • Resin composition, heat sealing agent, film for liquid packaging container, liquid packaging container, liquid discharge member, and medical container

    WO2017159800A1